Hollow particle containing elastomer

The hollow particle-containing elastomer composition addresses the issue of particle breakage and maintains dimensional stability by using a resin shell with a high crosslinkable monomer content and controlled mixing conditions, ensuring the properties and functions of the hollow particles are preserved.

CN119213064APending Publication Date: 2024-12-27ZEON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042742.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-05-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing elastomer compositions containing hollow particles face challenges in maintaining dimensional stability and preventing the breakage of hollow particles during the molding process, especially when mixed with a base elastomer, due to high shear forces, which impairs the properties and functions imparted by the hollow particles.

Method used

A hollow particle-containing elastomer composition is developed, comprising a base elastomer and hollow particles with a shell composed of a resin containing a high ratio of crosslinkable monomer units, where the storage modulus is maintained at 2.5 MPa or less, and the mixing process is conducted at a temperature that ensures minimal shear force, preserving the integrity of the hollow particles.

Benefits of technology

The composition maintains high dimensional stability and retains the properties and functions of the hollow particles, such as light weight, heat insulation, and shock absorption, by minimizing breakage during the molding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

Provided are: a hollow-particle-containing elastomer composition which maintains high dimensional stability during a molding step, and which is not susceptible to damage to characteristics or functions imparted by hollow particles; and a hollow-particle-containing elastomer composition which is not susceptible to breakage of the hollow particles during a kneading step for producing the elastomer composition, which has a stable pore residual rate, and which is not susceptible to damage to the characteristics or functions imparted by the hollow particles. And a manufacturing method in which the characteristics or functions imparted by the hollow particles are not susceptible to impairment. The hollow particle-containing elastomer composition according to the present invention comprises a base elastomer and hollow particles, the hollow particles having a shell containing a specific resin, and the hollow particle-containing elastomer composition having a storage modulus G'at 60 DEG C as determined by dynamic viscoelasticity measurement of 2.5 MPa or less. The residual void ratio measured by using the composition as a sheet-like molded article according to a predetermined test method is 80% or more. Furthermore, in the production method of the present invention, the starting material mixture is kneaded at a temperature at which the storage modulus G'is 2.5 MPa or less immediately after being pre-kneaded at a temperature at which the storage modulus G 'is 2.5 MPa or less, or after being further pre-heated at a temperature at which the storage modulus G' is 2.5 MPa or less, using a closed kneader, and then is kneaded at a temperature at which the storage modulus G 'is 2.5 MPa or less. The raw material mixture contains a base elastomer and hollow particles, the hollow particles have a shell containing a specific resin, and the storage modulus G'of the raw material mixture at 60 DEG C as determined by dynamic viscoelasticity measurement is 2.5 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an elastomer composition containing hollow particles and a method for preparing the same. Background Art

[0002] Elastomer products focus on the rubber-like elasticity and softness of elastomer raw materials represented by rubber, and are used in a wide range of fields for various purposes such as impact absorbers, fluid barrier fillers, and tubes. Generally, an elastomer composition in which necessary components are mixed with a base elastomer according to the application is kneaded in a molten state, and the base elastomer is cross-linked while being molded by extrusion molding, compression molding, etc., thereby obtaining elastomer products in various forms such as parts, coatings, and filling chip materials.

[0003] As a method for making an elastomer product lighter, there is known a method of mixing a foaming agent in a base elastomer, and foaming it by heating in a molding process to form a foamed elastomer molded body. In Patent Document 1, the purpose is to provide a rubber composition for vulcanization molding that can produce a rubber product with excellent dimensional stability, good surface properties, and effectively lightened. As a scheme that can achieve this purpose, a rubber composition for vulcanization molding obtained by mixing hollow particles with a base rubber having a specific Mooney viscosity at 100°C is recorded, wherein the hollow particles are composed of an outer shell and a foaming agent enclosed in the outer shell and vaporized by heating, and the expansion margin is 20 to 80%, wherein the outer shell is composed of a thermoplastic resin.

[0004] However, in the method of manufacturing a foamed elastic body by mixing a foaming agent with a base elastic body, it is difficult to control the size of the pores formed by foaming, so the dimensional stability of the obtained elastomer product is poor. The method of the above-mentioned patent document 1 sets obtaining a foamed elastic body with excellent dimensional stability as one of the technical issues, but it is required to further improve the dimensional stability.

[0005] As a method for introducing a plurality of fine pores into a molded body to impart properties or functions such as light weight, heat insulation, and opacity, it is known to use a molding material containing hollow particles in a base resin (Patent Documents 2 and 3). In a molding material containing hollow particles in a base resin, since the holes of the hollow particles contained in the molding material become pores, there is no need to control the size of the pores formed by foaming.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent No. 6116787;

[0009] Patent document 2: International Publication No. 2020 / 261926;

[0010] Patent document 3: International Publication No. 2021 / 112110. Summary of the invention

[0011] Problem that the invention aims to solve

[0012] The molding material containing hollow particles in the base elastomer is required to prevent the hollow particles from being easily broken during molding, maintain high dimensional stability, and prevent the characteristics or functions imparted by the hollow particles from being impaired.

[0013] In addition, in order to manufacture a molding material containing hollow particles in a base elastomer, it is required that the hollow particles are not easily broken when the raw material mixture containing the base elastomer and the hollow particles is kneaded. In particular, when the hollow particles are mixed with the base elastomer, since kneading with a strong shear force such as roll kneading is performed as the finishing kneading, a high shear force is generated compared to the case where the hollow particles are mixed with a base resin other than the elastomer and kneaded, and the hollow particles are easily broken during kneading.

[0014] The present invention has been made in view of the above problems, and an object of the present invention is to provide a hollow particle-containing elastomer composition in which the hollow particles are not easily broken during the molding process, high dimensional stability is maintained, and the properties or functions imparted by the hollow particles are not easily impaired.

[0015] In addition, the object of the present invention is to provide a method for producing a hollow particle-containing elastomer composition, in which the hollow particles are not easily broken during the step of kneading a raw material mixture containing a base elastomer and hollow particles, the porosity remaining rate after kneading is stable, and the characteristics or functions imparted by the hollow particles are not damaged by kneading.

[0016] Solutions for solving problems

[0017] The present invention provides a hollow particle-containing elastomer composition, which comprises at least a base elastomer and hollow particles.

[0018] The hollow particles have a shell composed of a resin and a hollow part surrounded by the shell, wherein the shell contains a polymer containing 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin.

[0019] The storage modulus G′ of the hollow particle-containing elastomer composition at 60° C. obtained by dynamic viscoelasticity measurement is 2.5 MPa or less.

[0020] The hollow particle-containing elastomer composition was used to prepare a sheet-shaped molded body according to the following method for measuring the residual porosity of a hollow particle-containing elastomer molded body, and the residual porosity was measured to be 80% or more.

[0021] [Method for measuring the residual porosity of hollow particle-containing elastomer molded body]

[0022] The hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to produce a sheet-shaped hollow particle-containing elastomer molded body.

[0023] The specific gravity of the obtained elastomer molded body was measured, and the porosity residual rate of the hollow particles in the elastomer molded body was calculated according to the following formula (D).

[0024] .

[0025] a: specific gravity of the sheet-like molded body after pressing;

[0026] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value);

[0027] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0028] In addition, the present invention provides a method for producing a hollow particle-containing elastomer composition, wherein the hollow particle-containing elastomer composition comprises at least a base elastomer and hollow particles. In the method for producing the hollow particle-containing elastomer composition,

[0029] A raw material mixture comprising at least a base elastomer and hollow particles is prepared, wherein the hollow particles have a shell comprising a resin and a hollow portion surrounded by the shell, the shell comprising a polymer comprising 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin, and the raw material mixture has a storage modulus G′ of 2.5 MPa or less at 60° C. obtained by dynamic viscoelasticity measurement after homogenization of the compounded components;

[0030] Using a closed-type mixer, pre-kneading the raw material mixture at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less;

[0031] The raw material mixture is kneaded at a temperature where the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less immediately after pre-mixing, or after preheating at a temperature where the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less.

[0032] Effects of the Invention

[0033] The hollow particle-containing elastomer composition of the present invention contains hollow particles whose strength is enhanced by virtue of the shell composed of a resin containing a polymer having a high content ratio of crosslinkable monomer units and whose strength is not reduced due to the crosslinked structure even in a high-temperature environment. Therefore, the hollow particles are not easily broken during the molding process, and high dimensional stability is maintained, and the characteristics or functions provided by the hollow particles are not easily impaired.

[0034] Therefore, according to the hollow particle-containing elastomer composition of the present invention, a hollow particle-containing molded body having high dimensional stability and excellent properties or functions can be obtained.

[0035] In addition, the method for producing the hollow particle-containing elastomer composition of the present invention uses hollow particles whose strength is improved by virtue of a shell composed of a resin containing a polymer with a high content ratio of cross-linkable monomer units, and whose strength does not decrease due to the cross-linked structure even in a high-temperature environment. Furthermore, the storage modulus G' of the raw material mixture containing the base elastomer and the hollow particles at 60°C is made to be less than 2.5 MPa, and pre-mixing and finishing mixing are carried out at a temperature at which the storage modulus G' of the raw material mixture becomes less than 2.5 MPa. As a result, loads such as internal pressure and shear force applied to the hollow particles inside the raw material mixture during mixing are suppressed to a low level.

[0036] Therefore, according to the production method of the present invention, the hollow particles are not easily broken in the kneading process, the residual porosity is stable, and the properties or functions imparted by the hollow particles are not easily damaged. Therefore, a hollow particle-containing elastomer composition having excellent properties or functions can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a diagram for explaining an example of a method for producing hollow particles used in the present invention.

[0038] Figure 2 The diagram is a schematic diagram showing one embodiment of a suspension in the suspension process. DETAILED DESCRIPTION

[0039] When the hollow particle-containing elastomer composition is used for molding, the hollow particles may be crushed due to the pressure or heat applied during molding.

[0040] Furthermore, when a raw material mixture containing a base elastomer and hollow particles is kneaded to produce a hollow particle-containing elastomer composition, the hollow particles may break. In particular, when the hollow particles are mixed with the base elastomer, a higher shear force is generated than when the hollow particles are mixed with a base resin other than the elastomer, so the hollow particles are easily broken during kneading.

[0041] In particular, when hollow particles having a large porosity are used, the shell thickness of the hollow particles is generally thin or the particle diameter is large, and thus the hollow particles are more easily broken.

[0042] The researchers of the present invention have found that when the storage modulus G′ of an elastomer composition formed by incorporating the following hollow particles into a base elastomer at 60°C is 2.5 MPa or less, the hollow particles are not easily broken when the elastomer composition is used for molding. Therefore, the porosity of the hollow particles existing inside the obtained elastomer molded body can be maintained, and the characteristics or functions imparted by the hollow particles are not easily damaged. The above-mentioned hollow particles have a shell composed of a resin, and the above-mentioned resin contains a polymer containing a certain amount or more of cross-linking monomer units.

[0043] Furthermore, the researchers of the present invention have found that when the storage modulus G′ at 60° C. measured after homogenizing a raw material mixture formed by blending the following hollow particles into a base elastomer is 2.5 MPa or less, the porosity of the hollow particles present in the elastomer composition obtained by kneading the raw material mixture can be maintained, and the characteristics or functions imparted by the hollow particles are not easily impaired. The above-mentioned hollow particles have a shell composed of a resin, and the above-mentioned resin contains a polymer containing a certain amount or more of a cross-linkable monomer unit.

[0044] The present invention has been accomplished based on the above findings.

[0045] The hollow particle-containing elastomer composition of the present invention is characterized in that it contains at least a base elastomer and hollow particles.

[0046] The hollow particles have a shell composed of a resin and a hollow part surrounded by the shell, wherein the shell contains a polymer containing 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin.

[0047] The storage modulus G′ of the hollow particle-containing elastomer composition at 60° C. obtained by dynamic viscoelasticity measurement is 2.5 MPa or less.

[0048] The hollow particle-containing elastomer composition was used to prepare a sheet-shaped molded body according to the following method for measuring the residual porosity of a hollow particle-containing elastomer molded body, and the residual porosity was measured to be 80% or more.

[0049] [Method for measuring the residual porosity of hollow particle-containing elastomer molded body]

[0050] The hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C., thereby producing a sheet-shaped hollow particle-containing elastomer molded body.

[0051] The specific gravity of the obtained elastomer molded body was measured, and the porosity residual rate of the hollow particles in the elastomer molded body was calculated according to the following formula (D).

[0052] .

[0053] a: specific gravity of the sheet-like molded body after pressing,

[0054] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value),

[0055] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0056] The method for producing a hollow particle-containing elastomer composition of the present invention is a method for producing the above-mentioned hollow particle-containing elastomer composition, characterized in that, in the method for producing a hollow particle-containing elastomer composition,

[0057] A raw material mixture comprising at least a base elastomer and hollow particles is prepared, wherein the hollow particles have a shell comprising a resin and a hollow portion surrounded by the shell, the shell comprising a polymer comprising 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin, and the raw material mixture has a storage modulus G′ of 2.5 MPa or less at 60° C. obtained by dynamic viscoelasticity measurement after homogenization of the compounded components;

[0058] Using a closed-type mixer, pre-kneading the raw material mixture at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less;

[0059] The raw material mixture is kneaded at a temperature where the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less immediately after pre-mixing, or after preheating at a temperature where the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less.

[0060] Hereinafter, the hollow particle-containing elastomer composition, the method for producing the hollow particle-containing elastomer composition, and the method for producing the elastomer molded article of the present invention will be described.

[0061] In the present invention, "to" in a numerical range means that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0062] Furthermore, in the present invention, (meth)acrylate represents each of acrylate and methacrylate, (meth)acrylic acid represents each of acrylic acid and methacrylic acid, and (meth)acryloyl represents each of acryloyl and methacryloyl.

[0063] In the present invention, a polymerizable monomer refers to a compound having a functional group capable of addition polymerization (sometimes referred to as a polymerizable functional group in the present invention). In the present invention, a compound having an ethylenically unsaturated bond as the functional group capable of addition polymerization is generally used as a polymerizable monomer.

[0064] In the present invention, a polymerizable monomer having only one polymerizable functional group is referred to as a non-crosslinking monomer, and a polymerizable monomer having two or more polymerizable functional groups is referred to as a crosslinking monomer. A crosslinking monomer is a polymerizable monomer that forms a crosslink bond in a resin by a polymerization reaction.

[0065] [Hollow particle-containing elastomer composition]

[0066] The hollow particle-containing elastomer composition of the present invention is a molding material for producing elastomer molded bodies such as elastomer parts, films, and core materials for fillings integrally molded with elastomer parts or parts of other materials by melt molding methods such as extrusion molding and compression molding.

[0067] The hollow particle-containing elastomer composition of the present invention can impart various properties such as light weight, heat insulation, low dielectric constant, light reflection and scattering, and retention of functional components such as antibacterial agents to the elastomer molded body by containing hollow particles. Therefore, as the use of the elastomer molded body manufactured using the elastomer composition, for example, light reflecting materials, heat insulating materials, sound insulating materials, and low dielectric materials used in various fields such as automobiles, electrical, electronic, construction, aviation, and aerospace, top coating materials or bottom coating materials requiring heat insulation, cushioning (shock absorption), light reflection, antibacterial properties, etc., cushioning materials (shock absorption materials) for shoes such as sports shoes and sandals, household appliance parts, bicycle parts, stationery, tools, hollow particle-containing filaments of 3D printers, buoyancy materials made of composite foam, etc. can be cited.

[0068] The hollow particle-containing elastomer composition of the present invention does not contain a foaming agent for making the elastomer molded body porous, but uses hollow particles that have been molded into a hollow shape. Therefore, the dimensional change of the elastomer molded body caused by foaming of the foaming agent does not occur.

[0069] Furthermore, since the hollow particle-containing elastomer composition of the present invention contains hollow particles whose strength is enhanced by virtue of the shell composed of a resin containing a polymer having a high content ratio of crosslinkable monomer units and whose strength is not reduced due to the crosslinked structure even in a high-temperature environment, the hollow particles are not easily broken during the molding process, and high dimensional stability is maintained, and the characteristics or functions imparted by the hollow particles are not easily impaired.

[0070] Therefore, according to the hollow particle-containing elastomer composition of the present invention, a hollow particle-containing molded body having high dimensional stability and excellent properties or functions can be obtained.

[0071] [Storage modulus]

[0072] From the viewpoint of reducing the breakage of hollow particles in the hollow particle-containing elastomer composition during kneading of the hollow particle-containing elastomer composition, the hollow particle-containing elastomer composition of the present invention is characterized in that the storage modulus at 60° C. obtained by dynamic viscoelasticity measurement is 2.5 MPa or less, preferably 1.7 MPa or less.

[0073] The lower limit of the storage elastic modulus G′ is not particularly limited, but is preferably 0.5 MPa or more, more preferably 0.8 MPa or more, in order to maintain the hardness of a molded body obtained from the elastomer composition.

[0074] The storage modulus of the hollow particle-containing elastomer composition at 60°C can be determined from the temperature dependence curve of the storage modulus obtained by measuring the dynamic viscoelasticity of the hollow particle-containing elastomer composition. In the present invention, a conventional method for measuring the dynamic viscoelasticity of a resin can be appropriately implemented, for example, the following method can be used.

[0075] [Method for dynamic viscoelasticity measurement]

[0076] The dynamic viscoelasticity measurement is performed using a measuring device such as HAAKE MARK III (manufactured by Thermo Fisher Scientific) or a rotating plate rheometer (model name ARES-G2, manufactured by TA Instruments) using a parallel plate or a cross-hatch plate under the following conditions.

[0077] <Measurement conditions>

[0078] Frequency: 1Hz

[0079] Geometry: Parallel plate or cross-hatched plate (20mmφ)

[0080] Sample group: After the test piece (2-4 mm thick) is welded to a 20 mmφ plate set at a temperature of 170°C, it is installed in a dynamic viscoelasticity measuring device. While cooling it from 170°C to room temperature (e.g. 25°C) at a rate of 5°C / min, the storage modulus G′ (unit: MPa) from 150°C to room temperature is measured.

[0081] Cooling speed: 5℃ / min

[0082] Temperature range: from 150°C to room temperature

[0083] Strain: 0.001

[0084] Gap: 1.5mm

[0085] The test piece can be prepared, for example, by using the hollow particle-containing elastomer composition of the present invention, preparing a 2 mm thick sheet on a press at 160° C., and punching out into a 20 mmφ shape using a punching machine.

[0086] [Method of adjusting storage modulus]

[0087] The storage modulus G′ of the hollow particle-containing elastomer composition obtained by dynamic viscoelasticity measurement at 60° C. can be adjusted by changing one or more of the factors such as the amount of plasticizer added, the amount of hollow particles added, the particle size of the hollow particles, the surface composition of the hollow particles, the type of organic or inorganic fine particles other than the hollow particles (e.g., carbon, silica, etc.), and the amount of organic or inorganic fine particles other than the hollow particles. Among the above factors, the amount of plasticizer added and the amount of hollow particles added can be factors that greatly change the storage modulus G′.

[0088] By increasing the amount of plasticizer added, the storage modulus G' of the hollow particle-containing elastomer composition can be reduced, and by reducing the amount of plasticizer added, the storage modulus G' of the hollow particle-containing elastomer composition can be increased. In order to adjust the storage modulus G' of the hollow particle-containing elastomer composition obtained by dynamic viscoelasticity measurement to 2.5 MPa or less, the amount of plasticizer added is usually increased or decreased appropriately within the range of 35 to 100 parts by mass, preferably 45 to 90 parts by mass relative to 100 parts by mass of the base elastomer.

[0089] In addition, the storage modulus G' of the hollow particle-containing elastomer composition can be increased by increasing the amount of hollow particles added, and the storage modulus G' of the hollow particle-containing elastomer composition can be reduced by reducing the amount of hollow particles added. Considering the balance with the contribution of the hollow particles to the purpose such as light weight, heat insulation, and shock absorption, and in order to adjust the storage modulus G' of the hollow particle-containing elastomer composition obtained by dynamic viscoelasticity measurement to 2.5 MPa or less, the amount of hollow particles added is usually appropriately increased or decreased within the range of 5 to 80 parts by mass relative to 100 parts by mass of the base elastomer.

[0090] [Base material elastomer]

[0091] As the substrate, an elastomer, that is, a polymer having rubber-like elasticity can be used. The elastomer is not particularly limited, and examples thereof include rubber and thermoplastic elastomer.

[0092] As the rubber, for example, natural rubber, isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), chloroprene rubber, acrylonitrile butadiene rubber, ethylene-α-olefin copolymer rubber, ethylene-propylene-diene terpolymer (EPDM) and other ethylene-α-olefin-non-conjugated diene copolymer rubbers, halogenated ethylene-α-olefin-non-conjugated diene copolymer rubbers, sulfonated ethylene-α-olefin-non-conjugated diene copolymer rubbers, maleated ethylene-α-olefin-non-conjugated diene copolymer rubbers, butyl rubber, isobutylene isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, polyurethane rubber, silicone rubber, chlorosulfonated polyethylene rubber, chlorinated polyethylene rubber, acrylic rubber, epichlorohydrin rubber, fluororubber, polysulfide rubber, propylene oxide rubber, etc. can be used.

[0093] In addition, thermoplastic elastomer refers to a substance that generally has the property of showing rubber-like elasticity at room temperature (25°C) and being plasticized and molded at high temperature. As the thermoplastic elastomer, thermoplastic elastic polymers that have been used as molding resins in the past can be used, and examples thereof include polyurethane elastomers, styrene elastomers, olefin elastomers, amide elastomers, and ester elastomers.

[0094] These substrate elastomers can use one or more than two. The substrate elastomer preferably includes at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, styrene butadiene rubber, natural rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, butyl rubber, fluororubber, silicone rubber, acrylonitrile butadiene rubber, chloroprene rubber, acrylic rubber, chlorosulfonated polyethylene rubber, chlorinated polyethylene rubber, polyurethane rubber, isobutylene isoprene rubber, polysulfide rubber, propylene oxide rubber and epichlorohydrin rubber, more preferably includes at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, styrene butadiene rubber, natural rubber, isoprene rubber and acrylic rubber, more preferably includes at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber and styrene butadiene rubber, more preferably includes ethylene-α-olefin-non-conjugated diene copolymer rubber.

[0095] Ethylene-α-olefin-non-conjugated diene copolymer rubber is a random copolymer of ethylene, α-olefin and non-conjugated diene. As α-olefin, propylene, 1-butene, 1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, etc. can be mentioned. Among these, propylene, 1-hexene, 1-octene are preferred, and propylene is particularly preferred. These α-olefins can be used one or two or more. The molar ratio of ethylene to α-olefin (ethylene / α-olefin) is not particularly limited, preferably 40 / 60 to 95 / 5, more preferably 50 / 50 to 85 / 15, and more preferably 60 / 40 to 80 / 20.

[0096] As non-conjugated dienes, 1,4-hexadiene, 3-methyl-1,4-hexadiene, 1,7-octadiene, 1,9-decadiene, 5-ethylidene-2-norbornene, 5-isopropylidene-2-norbornene, 5-isobutylene-2-norbornene, cyclopentadiene, dicyclopentadiene, norbornadiene, etc. can be cited. Among these, 5-ethylidene-2-norbornene and dicyclopentadiene are preferred. These non-conjugated dienes can be used alone or in combination of two or more.

[0097] Examples of butadiene rubber (BR) include low cis BR, high cis BR, high trans BR, etc. In addition, as butadiene rubber, modified BR introduced with nitrogen atom-containing functional groups, silicon atom-containing functional groups, oxygen atom-containing functional groups, etc. may also be used.

[0098] As styrene butadiene rubber (SBR), solution polymerization SBR, emulsion polymerization SBR etc. can be enumerated. In addition, as styrene butadiene rubber, acid-modified SBR can also be used. As commercially available products of acid-modified SBR, trade name Nipol LX206 (made by Japan Zeon Co., Ltd.), trade name Nipol LX209 (made by Japan Zeon Co., Ltd.), trade name BM-430B (made by Japan Zeon Co., Ltd.), trade name BM-451B (made by Japan Zeon Co., Ltd.) can be enumerated.

[0099] When at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber and styrene-butadiene rubber is used as at least a part of the base elastomer, the mass ratio of the rubber selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber and styrene-butadiene rubber in the base elastomer as a whole is preferably 50 mass % or more, more preferably 70 mass % or more, and further preferably 90 mass % or more. The preferred upper limit of the mass ratio of the rubber selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber and styrene-butadiene rubber in the base elastomer as a whole is 100 mass %.

[0100] The mass ratio of ethylene-α-olefin-non-conjugated diene copolymer rubber in the whole base elastomer is preferably 50 mass % or more, more preferably 70 mass % or more, and further preferably 90 mass % or more. The preferred upper limit of the mass ratio of ethylene-α-olefin-non-conjugated diene copolymer rubber in the whole base elastomer is 100 mass %.

[0101] The iodine value of the base elastomer is not particularly limited, but is preferably 5 to 50 g / 100 g, more preferably 10 to 40 g / 100 g, and further preferably 15 to 30 g / 100 g. When the iodine value of the base elastomer is within the above range, an elastomer composition having high crosslinking efficiency can be obtained, and an elastomer composition capable of providing a vulcanized elastomer product having excellent compression set resistance and excellent environmental degradation resistance can be obtained.

[0102] In the case where the base elastomer includes an elastomer having a styrene monomer unit such as styrene-butadiene rubber or a styrene-based thermoplastic elastomer, the rigidity of the elastomer composition of the present invention can be adjusted by changing the content of the styrene monomer unit in the base elastomer. However, when the content of the styrene monomer unit in the base elastomer is too high, the rigidity of the elastomer composition and its raw material mixture when melt-kneading is also increased, so it may be difficult to make the storage modulus G' sufficiently low during melt-kneading. Therefore, the content ratio of the styrene monomer unit contained in the base elastomer is preferably 0% by mass or more and 60% by mass or less of the total mass of the base elastomer, and more preferably 0% by mass or more and 50% by mass or less.

[0103] From the viewpoint of improving the dimensional stability and surface properties of a molded article produced from the elastomer composition of the present invention, the Mooney viscosity (ML (1+4) 100°C) of the base elastomer measured in accordance with JIS K6300 is preferably 20 to 75, more preferably 20 to 60, and even more preferably 20 to 55.

[0104] In the above expression "ML(1+4)100°C" related to Mooney viscosity, "M" represents Mooney unit, "L" represents that the rotor shape is L-type, "1+4" represents that the preheating time is 1 minute and the rotor rotation time is 4 minutes, and "100°C" represents that the measuring temperature is 100°C.

[0105] [Hollow particles]

[0106] The hollow particles used in the present invention are particles having a shell (outer shell) containing a resin and a hollow portion surrounded by the shell.

[0107] In the present invention, the hollow part is a hole-like space clearly distinguished from the shell of the hollow particle formed by the resin material. The shell of the hollow particle may have a porous structure, in which case the hollow part has a size that can be clearly distinguished from a plurality of micro spaces uniformly dispersed in the porous structure. From the viewpoint of pressure resistance, etc., the hollow particle of the present invention preferably has a dense shell.

[0108] The hollow part of the hollow particles can be confirmed by, for example, SEM observation of a particle cross section or TEM observation of the particles directly.

[0109] Furthermore, the hollow part of the hollow particles of the present invention may be filled with a gas such as air, may be in a vacuum or reduced pressure state, and may contain a solvent.

[0110] The hollow particles used in the present invention are improved in strength by virtue of the shell composed of a resin of a polymer with a high content ratio including a cross-linked monomer unit, and the strength will not be reduced due to the cross-linked structure even in a high temperature environment, therefore, the hollow particles used in the present invention are excellent in pressure resistance, and are not easily broken during mixing with other materials and molding after mixing. When added to a molded body, they impart various effects such as lightweight, heat insulation, sound insulation, shock absorption, and light scattering. In addition, as other uses, since the useful components such as spices, medicines, pesticides, and ink components can be enclosed in the hollow interior by means such as impregnation treatment, decompression, or pressurized impregnation treatment, the effect of the encapsulation material is excellent, so it is suitable for use as a molded body additive. In addition, the hollow particles used in the present invention are not easily broken, and the porosity is not easily reduced even after mixing, injection molding, and other processes that apply external pressure, shear force, and other loads, therefore, they are particularly suitable for use as an additive for a molded body obtained by a process that applies a load.

[0111] The porosity of the hollow particles used in the present invention is preferably 50% or more, more preferably 60% or more, and more preferably 65% ​​or more. By having a porosity of more than the above lower limit, the characteristics such as lightness, heat resistance, heat insulation and dielectric properties are also excellent. The upper limit of the porosity of the hollow particles is not particularly limited, and from the viewpoint of suppressing the reduction of the pressure resistance of the hollow particles, it is preferably 90% or less, more preferably 85% or less, and more preferably 80% or less.

[0112] The porosity of the hollow particles is calculated from the apparent density D1 and true density D0 of the hollow particles.

[0113] The apparent density D1 of the hollow particles is measured as follows. First, in a volume of 100 cm 3 Fill the volumetric flask to about 30 cm 3 Next, fill the volumetric flask filled with hollow particles with isopropyl alcohol to a marked capacity of 100 cm while taking care not to introduce air bubbles.3 The mass of isopropanol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm 3 ).

[0114] Formula (I):

[0115] .

[0116] The apparent density D1 corresponds to the specific gravity of the entire hollow particle when the hollow portion is regarded as a part of the hollow particle.

[0117] The true density D0 of the hollow particles is determined as follows. The hollow particles are crushed in advance and then placed in a container with a volume of 100 cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed. Then, isopropyl alcohol is added to the volumetric flask in the same manner as the above-mentioned apparent density measurement, and the mass of isopropyl alcohol is accurately weighed. The true density D0 (g / cm 3 ).

[0118] Formula (II):

[0119] .

[0120] The true density D0 corresponds to the specific gravity of only the shell portion of the hollow particle. As is apparent from the above-described measurement method, when calculating the true density D0, the hollow portion is not considered as a part of the hollow particle.

[0121] The porosity (%) of the hollow particles is calculated by the following formula (III) from the apparent density D1 and the true density D0 of the hollow particles.

[0122] Formula (III):

[0123] .

[0124] The degree of crushing ease of the hollow particles can be expressed by the residual porosity measured by the following compression test method.

[0125] [Compression test method]

[0126] A mixture of polypropylene resin and hollow particles having a mass ratio of polypropylene resin to hollow particles of 90:10 was melted and mixed at 200°C, placed in a hot press mold, heated at 200°C for 15 minutes and stirred, then loaded on a hot press set at 80°C, a barrel heated to 80°C was placed in the mold, and when the surface temperature of the mold reached 140°C, the mixture was pressurized at 15MPa, and then taken out of the mold, and pressed at a pressure of 1MPa or less by a hot press set at 200°C to form a sheet. The specific gravity of the obtained sheet-like molded body was measured, and the porosity residual rate of the hollow particles was calculated according to the following formula (D).

[0127] .

[0128] The symbols in formula (D) have the following meanings.

[0129] a: specific gravity of the sheet-like molded body after compression molding,

[0130] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value),

[0131] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0132] The specific gravity of the molded body after press molding was measured by a water displacement method in accordance with JIS K 7112.

[0133] The "molded body assuming that the porosity is maintained" means a molded body assuming that the hollow particles mixed with the polypropylene resin are not broken in the molded body after the hot pressing step and the porosity before mixing is maintained. The specific gravity b of the molded body assuming that the porosity is maintained is calculated by the following formula (E).

[0134] .

[0135] In the calculation formula for the above b, P A Indicates the amount of hollow particles added, P G Indicates the specific gravity of hollow particles, R A Indicates the amount of base elastomer added, R G Indicates the specific gravity of the base elastomer.

[0136] The specific gravity c of the molded body assuming that all hollow particles are crushed is calculated by the following formula (F).

[0137] .

[0138] In the calculation formula for the above c, R A Indicates the amount of base elastomer added, R Grepresents the specific gravity of the base material elastomer, D0 represents the true density of the hollow particles, P A Indicates the amount of hollow particles added, P V It represents the porosity of hollow particles (%).

[0139] As the polypropylene resin used in the above-mentioned press test, a polypropylene resin having an MFR (melt flow rate) of 10 to 30 g / min, preferably 15 to 25 g / min at 230° C. can be used. Commercially available products of such polypropylene resins include, for example, Novatec PP, grade MA1B (MFR at 230° C.: 21 g / min) manufactured by Japan Polypropylene Co., Ltd.

[0140] The larger the above-mentioned residual porosity is, the less likely the hollow particles are to break during the production of the hollow particle-containing elastomer composition and the production of an elastomer molded body using the hollow particle-containing elastomer composition, the more the effect imparted by the hollow particles can be maintained without being reduced, and the higher the dimensional stability during molding. In the case where the hollow particles are not broken at all, the residual porosity is 100%.

[0141] The hollow particles used in the present invention can make the porosity residual rate using the above test method reach more than 80%, and can also reach 100%.

[0142] The lower limit of the volume average particle size of the hollow particles used in the present invention is preferably 5.0 μm or more, more preferably 6.0 μm or more, and more preferably 7.0 μm or more. The upper limit of the volume average particle size of the hollow particles used in the present invention is preferably 40.0 μm or less, more preferably 30.0 μm or less, and more preferably 20.0 μm or less. When the volume average particle size of the hollow particles is above the above lower limit, it is easy to take into account both high porosity and excellent pressure resistance, and the cohesion of the hollow particles becomes small, so that excellent dispersibility can be exerted. When the volume average particle size of the hollow particles is below the above upper limit, the uniformity of the shell is easily improved, so it is easy to obtain hollow particles with excellent pressure resistance.

[0143] The particle size of the hollow particles of the present invention can be adjusted by, for example, the content of the dispersion stabilizer relative to the total mass of the polymerizable monomer and the hydrophobic solvent.

[0144] The shell thickness of the hollow particles used in the present invention is not particularly limited. From the viewpoint of improving pressure resistance, it is preferably 0.30 μm or more, more preferably 0.40 μm or more, further preferably 0.50 μm or more, and further preferably 0.60 μm or more. From the viewpoint of improving porosity, it is preferably 3.00 μm or less, more preferably 2.00 μm or less, and further preferably 1.50 μm or less.

[0145] In addition, in the present invention, the shell thickness of the hollow particles is a value obtained by the following calculation, that is, the inner diameter r of the hollow particles is calculated using the volume average particle diameter R and porosity of the hollow particles by the following formula (1), and the inner diameter r and the volume average particle diameter R are used to calculate the shell thickness by the following formula (2).

[0146] Formula (1):

[0147] .

[0148] Formula (2):

[0149] .

[0150] In addition, the porosity in the above formula (1) is a numerical value expressed as a percentage.

[0151] The particle size distribution (volume average particle size (Dv) / number average particle size (Dn)) of the hollow particles used in the present invention can be, for example, 1.1 or more and 2.5 or less. By having the particle size distribution be 2.5 or less, particles with small unevenness in compressive strength characteristics and heat resistance between particles can be obtained. In addition, by having the particle size distribution be 2.5 or less, when, for example, a sheet-like molded body to which the hollow particles of the present invention are added is manufactured, a product with uniform thickness can be manufactured.

[0152] The volume average particle size (Dv) and number average particle size (Dn) of the hollow particles can be measured by, for example, a particle size distribution measuring device to measure the particle size of the hollow particles, and the number average and volume average are calculated, respectively, and the obtained values ​​are used as the number average particle size (Dn) and volume average particle size (Dv) of the particles. The particle size distribution is the value obtained by dividing the volume average particle size by the number average particle size.

[0153] The shape of the hollow particles used in the present invention is not particularly limited as long as a hollow portion is formed inside, and examples thereof include spherical, ellipsoidal, and irregular shapes, etc. Among these, a spherical shape is preferred from the viewpoint of ease of production and pressure resistance.

[0154] The hollow particles used in the present invention may have one or more hollow parts, and from the viewpoint of maintaining a good balance between high porosity and mechanical strength, preferably only have one or two hollow parts, preferably only have one hollow part. In the hollow particles used in the present invention, the number ratio of particles having only one hollow part is preferably 90% or more, more preferably 95% or more, and further preferably greater than 95%.

[0155] Furthermore, the shell of the hollow particle and, when the hollow particle has two or more hollow parts, the partition wall separating adjacent hollow parts may be porous, but is preferably dense from the viewpoint of improving pressure resistance.

[0156] The average circularity of the hollow particles used in the present invention may be 0.950 to 0.995.

[0157] An example of the shape of the hollow particles of the present invention is a bag formed by a thin membrane and bulged by gas, and its cross-sectional view is as follows: Figure 1 The hollow particle 10 in (5) is shown. In this example, a thin film is provided on the outside, and the inside is filled with gas.

[0158] In addition, the particle shape can be confirmed by, for example, SEM or TEM.

[0159] Furthermore, the thermal decomposition starting temperature of the hollow particles of the present invention is preferably 150 to 400° C., and more preferably 200 to 350° C. The hollow particles having a thermal decomposition starting temperature within the above range have excellent heat resistance.

[0160] The thermal decomposition starting temperature of the hollow particles refers to the temperature at which the mass decreases by 5%, and can be measured by a TG-DTA apparatus under air atmosphere at an air flow rate of 230 mL / min and a temperature increase rate of 10° C. / min.

[0161] The content of the hollow particles in the elastomer composition is not particularly limited, but is usually 5 to 80 parts by mass based on 100 parts by mass of the base elastomer.

[0162] Hereinafter, an example of a method for producing hollow particles used in the present invention will be described in detail.

[0163] The hollow particles can be obtained by, for example, a production method including the following steps: preparing a mixed solution containing a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium;

[0164] A step of suspending the mixed liquid to prepare a suspension in which droplets of a monomer composition containing the polymerizable monomer, the hydrophobic solvent and the polymerization initiator are dispersed in the aqueous medium;

[0165] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition including precursor particles having a hollow portion surrounded by a shell containing a resin and containing the hydrophobic solvent in the hollow portion.

[0166] The above-mentioned manufacturing method follows the following basic technology: by suspending a mixed liquid containing a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer and an aqueous medium, a suspension is prepared in which droplets having the following distribution structure are dispersed in an aqueous medium, wherein the polymerizable monomer and the hydrophobic solvent are phase-separated, the polymerizable monomer is biased toward the surface side, and the hydrophobic solvent is biased toward the center, and the suspension is supplied to a polymerization reaction, thereby solidifying the surface of the droplets to form hollow particles having a hollow portion filled with the hydrophobic solvent.

[0167] It is speculated that in the above basic technology, by adjusting the composition of the polymerizable monomer and the type of the hydrophobic solvent, etc., the polymerizable monomer and the hydrophobic solvent are sufficiently phase-separated in the droplets of the monomer composition dispersed in the suspension, and when the suspension is supplied to the polymerization reaction, the polymerization reaction of the polymerizable monomer proceeds uniformly, thereby forming a shell with excellent uniformity in composition and thickness.

[0168] The method for producing hollow particles includes a process of preparing a mixed solution, a process of preparing a suspension, and a process of supplying the suspension to a polymerization reaction, and may further include processes other than these. In addition, as long as it is technically feasible, two or more of the above-mentioned processes and other additional processes may be performed simultaneously as a process, or the order may be reversed. For example, the material for preparing the mixed solution may be added while the suspension is performed simultaneously, so that the preparation and suspension of the mixed solution are performed simultaneously in one process.

[0169] As a preferred example of a method for producing hollow particles, there can be mentioned a method including the following steps.

[0170] (1) Mixed solution preparation process

[0171] A step of preparing a mixed solution comprising a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium;

[0172] (2) Suspension process

[0173] A step of suspending the mixed solution to prepare a suspension in which droplets of a monomer composition containing a polymerizable monomer, a hydrophobic solvent, and a polymerization initiator are dispersed in an aqueous medium;

[0174] (3) Polymerization process

[0175] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion surrounded by a shell containing a resin and containing a hydrophobic solvent in the hollow portion;

[0176] (4) Solid-liquid separation process

[0177] A step of separating the precursor composition into solid and liquid to obtain precursor particles containing a hydrophobic solvent in a hollow portion;

[0178] (5) Solvent Removal Process

[0179] A step of removing the hydrophobic solvent contained in the precursor particles obtained in the solid-liquid separation step to obtain hollow particles.

[0180] In the present invention, hollow particles whose hollow parts are filled with a hydrophobic solvent are sometimes referred to as “precursor particles”, assuming that they are intermediates of hollow particles whose hollow parts are filled with a gas. In the present invention, “precursor composition” refers to a composition containing precursor particles.

[0181] Figure 1 This is a schematic diagram showing an example of the production method of the present invention. Figure 1 (1) to (5) in the figure correspond to the above steps (1) to (5). The white arrows between the figures indicate the order of the steps. Figure 1 The schematic diagrams are only for explanation, and the manufacturing method of the present invention is not limited to the manufacturing method shown in the figures. In addition, the structure, size and shape of the materials used in the manufacturing method of the present invention are not limited to the structure, size and shape of the various materials in these figures.

[0182] Figure 1 (1) is a cross-sectional schematic diagram showing an embodiment of a mixed solution in a mixed solution preparation process. As shown in the figure, the mixed solution includes an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material with low polarity that is not easily mixed with the aqueous medium 1. In the present invention, the low-polarity material 2 includes a polymerizable monomer, a hydrophobic solvent, and a polymerization initiator.

[0183] Figure 1 (2) is a cross-sectional schematic diagram showing an embodiment of the suspension in the suspension process. The suspension includes an aqueous medium 1 and droplets 8 of a monomer composition dispersed in the aqueous medium 1. The droplets 8 of the monomer composition include polymerizable monomers, a hydrophobic solvent, and a polymerization initiator, but the distribution in the droplets is uneven. The droplets 8 of the monomer composition have the following structure: the hydrophobic solvent 4a is separated from the material 4b other than the hydrophobic solvent including the polymerizable monomer, the hydrophobic solvent 4a is biased in the center, the material 4b other than the hydrophobic solvent is biased on the surface side, and a dispersion stabilizer (not shown) is attached to the surface.

[0184] Figure 1(3) is a schematic cross-sectional view showing an embodiment of a precursor composition containing precursor particles obtained by a polymerization process, wherein the precursor particles contain a hydrophobic solvent in a hollow portion. The precursor composition comprises an aqueous medium 1 and precursor particles 9 containing a hydrophobic solvent 4a in a hollow portion dispersed in the aqueous medium 1. The shell 6 forming the outer surface of the precursor particle 9 is formed by polymerization of the polymerizable monomer in the droplets 8 of the monomer composition, and the shell 6 contains a polymer of the polymerizable monomer as a resin.

[0185] Figure 1 (4) is a schematic cross-sectional view showing one embodiment of the precursor particles after the solid-liquid separation step. Figure 1 (4) shows that from the above Figure 1 The state (3) is the state after removing the aqueous medium 1.

[0186] Figure 1 (5) is a schematic cross-sectional view showing one embodiment of the hollow particles after the solvent removal step. Figure 1 (5) shows that from the above Figure 1 The state (4) is the state after the hydrophobic solvent 4a is removed. By removing the hydrophobic solvent from the precursor particles, hollow particles 10 having a hollow part 7 filled with gas inside the shell 6 can be obtained.

[0187] Hereinafter, the above five steps and other steps will be described in sequence.

[0188] (1) Mixed solution preparation process

[0189] This step is a step of preparing a mixed solution containing a polymerizable monomer, a hydrophobic solvent, a polymerization initiator, a dispersion stabilizer, and an aqueous medium. The mixed solution may further contain other materials within a range that does not impair the effects of the present invention.

[0190] The materials of the mixed solution are described in order: (A) polymerizable monomer, (B) hydrophobic solvent, (C) polymerization initiator, (D) dispersion stabilizer, and (E) aqueous medium.

[0191] (A) Polymerizable Monomer

[0192] As the polymerizable monomer, a known polymerizable monomer used in the preparation of hollow particles can be used, without particular limitation, and at least a portion of the polymerizable monomer includes a crosslinking monomer. When the polymerizable monomer includes a crosslinking monomer, the crosslinking density of the shell can be increased, and therefore, a shell with excellent strength can be easily formed, the hollow particles can easily become spherical, and a hollow portion that can be clearly distinguished from the shell can be easily formed in the particle.

[0193] In addition, from the viewpoint that the polymerization reaction is easy to be stable, as the polymerizable monomer, a polymerizable monomer having a polymerizable functional group of (meth) acryloyl or vinyl is preferred, and an acrylic monomer containing a (meth) acryloyl as a polymerizable functional group is more preferred. In addition, in the present invention, stable polymerization reaction means that the reactivity of the polymerization reaction is good and the polymerization reaction proceeds uniformly.

[0194] In addition, when the polymerizable monomer includes an acrylic monomer and a hydrocarbon monomer, not only the polymerization reaction is easy to be stable, but also the pressure resistance of the hollow particles can be improved, so it is particularly preferred. It is speculated that by copolymerizing the acrylic monomer and the hydrocarbon monomer, the reaction rate of the hydrocarbon monomer increases, and therefore, the reactivity of the polymerizable monomer as a whole is improved, and as a result, the polymerization reaction is easy to be stable. In addition, it is speculated that when the polymerizable monomer includes an acrylic monomer and a hydrocarbon monomer, the compatibility of the polymerizable monomer and the hydrophobic solvent becomes appropriate, and thus when the suspension is supplied to the polymerization reaction, the polymerization reaction of the polymerizable monomer is easy to be carried out uniformly, and the shell formed is easy to become a shell with excellent uniformity such as composition and thickness, and therefore, the pressure resistance of the hollow particles is improved.

[0195] As the hydrocarbon monomer, it is preferred that the polymerizable functional group is a vinyl group from the viewpoint of easy and stable polymerization reaction.

[0196] In the present invention, a polymerizable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as an acrylic monomer, a crosslinkable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as a crosslinkable acrylic monomer, and a non-crosslinkable monomer having a (meth)acryloyl group as a polymerizable functional group is referred to as a non-crosslinked acrylic monomer. In the crosslinkable acrylic monomer, at least one polymerizable functional group may be a (meth)acryloyl group, and preferably all polymerizable functional groups are (meth)acryloyl groups.

[0197] In the present invention, a polymerizable monomer composed of carbon and hydrogen is referred to as a hydrocarbon monomer, a crosslinkable monomer composed of carbon and hydrogen is referred to as a crosslinkable hydrocarbon monomer, and a non-crosslinkable monomer composed of carbon and hydrogen is referred to as a non-crosslinkable hydrocarbon monomer.

[0198] As the cross-linkable monomer used in the production method of the present invention, a cross-linkable acrylic monomer and a cross-linkable hydrocarbon monomer are preferred.

[0199] Examples of the crosslinkable acrylic monomer include bifunctional crosslinkable acrylic monomers such as allyl (meth)acrylate, vinyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, and 2-hydroxy-3-(meth)acryloylpropyl (meth)acrylate; and trifunctional or higher crosslinkable acrylic monomers such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, and ethoxylates thereof.

[0200] Examples of the crosslinkable hydrocarbon monomer include bifunctional crosslinkable hydrocarbon monomers such as divinylbenzene, divinyldiphenyl, and divinylnaphthalene.

[0201] Furthermore, as the crosslinkable monomer, there can be mentioned crosslinkable allyl monomers such as diallyl phthalate.

[0202] These crosslinking monomers can be used alone or in combination of two or more.

[0203] From the viewpoint of improving the shell strength and obtaining hollow particles having excellent pressure resistance, the crosslinkable monomer preferably includes a trifunctional or higher crosslinkable monomer having three or more polymerizable functional groups.

[0204] As the trifunctional or higher crosslinking monomer, the above-mentioned trifunctional or higher crosslinking acrylic monomers are preferred, and pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol poly(meth)acrylate are particularly preferred, and pentaerythritol tetra(meth)acrylate and trimethylolpropane tri(meth)acrylate are more preferred.

[0205] From the viewpoint of improving the shell strength and obtaining hollow particles with excellent pressure resistance, it is more preferred that the crosslinking monomer include a bifunctional crosslinking monomer having only two polymerizable functional groups and a trifunctional or higher crosslinking monomer having three or more polymerizable functional groups.

[0206] As the bifunctional crosslinkable monomer, at least one selected from the above-mentioned bifunctional crosslinkable acrylic monomers and the above-mentioned bifunctional crosslinkable hydrocarbon monomers is preferred.

[0207] As the bifunctional crosslinkable acrylic monomer, ethylene glycol di(meth)acrylate and pentaerythritol di(meth)acrylate are particularly preferred, and ethylene glycol di(meth)acrylate is more preferred.

[0208] As the bifunctional crosslinkable hydrocarbon monomer, divinylbenzene is particularly preferred.

[0209] From the viewpoint of improving the pressure resistance of hollow particles, in 100 parts by mass of polymerizable monomers, the content of crosslinkable monomers is 50 parts by mass or more, more preferably 60 parts by mass or more, further preferably 70 parts by mass or more, and further preferably 80 parts by mass or more. When the content of crosslinkable monomers is above the above lower limit, a hollow portion is easily formed in the particles, and the particles are easily spherical, thereby being able to increase the crosslinking density of the shell, and therefore, it also has the advantage of being able to improve the solvent resistance, strength, heat resistance, etc. of the hollow particles. On the other hand, within the scope of not impairing the effect of the present invention, the polymerizable monomers may contain non-crosslinkable monomers, in which case, in 100 parts by mass of polymerizable monomers, the content of crosslinkable monomers may be, for example, 95 parts by mass or less, or 90 parts by mass or less.

[0210] In addition, the content of the crosslinkable monomer refers to the total content of the bifunctional crosslinkable monomer and the trifunctional or higher crosslinkable monomer.

[0211] When the cross-linking monomer contains a trifunctional or higher cross-linking monomer, from the viewpoint of improving the pressure resistance of the hollow particles, the lower limit of the content of the trifunctional or higher cross-linking monomer in 100 parts by mass of the polymerizable monomer is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and the upper limit of the content of the trifunctional or higher cross-linking monomer is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 30 parts by mass or less.

[0212] In the case where the crosslinkable monomer includes a bifunctional crosslinkable monomer and a trifunctional or higher crosslinkable monomer, from the viewpoint of improving the pressure resistance of the hollow particles, the lower limit of the content of the trifunctional crosslinkable monomer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 20 parts by mass or more, and the upper limit of the content of the trifunctional crosslinkable monomer is preferably 50 parts by mass or less, and more preferably 40 parts by mass or less, relative to 100 parts by mass of the total mass of the bifunctional crosslinkable monomer and the trifunctional or higher crosslinkable monomer.

[0213] In the range that does not impair the effect of the present invention, the polymerizable monomer may also include a non-crosslinking monomer. As the non-crosslinking monomer, for example, alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide, etc., non-crosslinking acrylic monomers; aromatic vinyl monomers such as styrene, vinyl toluene, α-methylstyrene, p-methylstyrene, ethylvinylbenzene, ethylvinylbiphenyl, and ethylvinylnaphthalene, monoolefin monomers such as ethylene, propylene, and butene, and non-crosslinking hydrocarbon monomers such as diene monomers such as butadiene and isoprene; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated aromatic vinyl monomers such as halogenated styrene; halogenated vinyl monomers such as vinyl chloride; vinylidene halide monomers such as vinylidene chloride; vinyl pyridine monomers, etc. These non-crosslinking monomers can be used alone or in combination of two or more.

[0214] As the non-crosslinking monomer, from the viewpoint of stabilizing the polymerization reaction and suppressing the decrease in the pressure resistance of the hollow particles, alkyl (meth)acrylates and aromatic vinyl monomers are particularly preferred, and aromatic vinyl monomers are more preferred. As the alkyl (meth)acrylates, butyl acrylate and methyl methacrylate are particularly preferred. As the aromatic vinyl monomer, ethyl vinylbenzene is particularly preferred.

[0215] From the viewpoint of improving the stability of the polymerization reaction, the content of the acrylic monomer in 100 parts by mass of the polymerizable monomer is preferably 10 parts by mass or more, and more preferably 20 parts by mass or more.

[0216] In addition, from the viewpoint of improving the stability of the polymerization reaction and the viewpoint of improving the pressure resistance of the hollow particles, the content of the acrylic monomer and the hydrocarbon monomer in 100 parts by mass of the polymerizable monomer is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 98 parts by mass or more, and further preferably 99 parts by mass or more.

[0217] When the polymerizable monomer contains an acrylic monomer and a hydrocarbon monomer, from the viewpoint of improving the pressure resistance of the hollow particles, the lower limit of the content of the hydrocarbon monomer is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and further preferably 30 parts by mass or more, relative to 100 parts by mass of the total of the acrylic monomer and the hydrocarbon monomer, and the upper limit of the content of the hydrocarbon monomer is preferably 90 parts by mass or less, and more preferably 80 parts by mass or less.

[0218] The content of the polymerizable monomer in the mixed solution is not particularly limited. From the viewpoint of the balance among the porosity, particle size and mechanical strength of the hollow particles, the lower limit of the content of the polymerizable monomer in the mixed solution is preferably 30% by mass or more, more preferably 40% by mass or more, relative to 100% by mass of the total mass of the components in the mixed solution excluding the aqueous medium, and the upper limit of the content of the polymerizable monomer in the mixed solution is preferably 60% by mass or less, more preferably 50% by mass or less.

[0219] Furthermore, from the viewpoint of the mechanical strength of the hollow particles, the content of the polymerizable monomer is preferably 95% by mass or more, more preferably 97% by mass or more, relative to 100% by mass of the total mass of the solid components excluding the hydrophobic solvent in the material forming the oil phase in the mixed liquid.

[0220] In the present invention, the solid content refers to all components except the solvent, and liquid polymerizable monomers and the like are included in the solid content.

[0221] (B) Hydrophobic solvent

[0222] The hydrophobic solvent used in the production method of the present invention is a non-polymerizable organic solvent that is poorly soluble in water.

[0223] The hydrophobic solvent acts as a spacer material for forming a hollow portion inside the particle. In the suspension process described later, a suspension obtained by dispersing droplets of a monomer composition containing a hydrophobic solvent in an aqueous medium can be obtained. In the suspension process, phase separation occurs in the droplets of the monomer composition, and as a result, the hydrophobic solvent with low polarity easily gathers inside the droplets of the monomer composition. Finally, in the droplets of the monomer composition, the hydrophobic solvent is distributed inside according to their respective polarities, and other materials except the hydrophobic solvent are distributed around them.

[0224] In the polymerization step described below, an aqueous dispersion containing precursor particles containing a hydrophobic solvent can be obtained. That is, as the hydrophobic solvent accumulates inside the particles, a hollow portion filled with the hydrophobic solvent is formed inside the obtained precursor particles.

[0225] The hydrophobic solvent can be appropriately selected from known hydrophobic solvents without particular limitation, and examples thereof include esters such as ethyl acetate and butyl acetate; ether esters such as propylene glycol monomethyl ether acetate and propylene glycol monoethyl ether acetate; and hydrocarbon solvents. In particular, hydrocarbon solvents can be preferably used.

[0226] Examples of hydrocarbon solvents include aliphatic hydrocarbons including chain hydrocarbon solvents such as pentane, hexane, heptane, octane, 2-methylbutane and 2-methylpentane, and cyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane and cycloheptane; and aromatic hydrocarbons such as benzene, toluene and xylene.

[0227] These hydrophobic solvents can be used alone or in combination of two or more.

[0228] From the viewpoint of facilitating phase separation of the polymerizable monomer and the hydrophobic solvent in the droplets of the monomer composition in the suspension step, it is preferred to select an organic solvent having a lower solubility in water than the crosslinking monomer included in the polymerizable monomer as the hydrophobic solvent.

[0229] In addition, when the polymerizable monomers include acrylic monomers and hydrocarbon monomers, a chain hydrocarbon solvent is preferably used as the hydrophobic solvent. As the chain hydrocarbon solvent, a chain hydrocarbon solvent having 5 to 8 carbon atoms is particularly preferred, and at least one selected from pentane, hexane, heptane and octane is more preferred.

[0230] On the other hand, when the polymerizable monomer contains an acrylic monomer but does not contain a hydrocarbon monomer, as the hydrophobic solvent, it is preferred to use a hydrocarbon solvent having 4 to 7 carbon atoms, and more preferably a hydrocarbon solvent having 5 to 7 carbon atoms. Here, the hydrocarbon solvent may be an aromatic hydrocarbon or an aliphatic hydrocarbon, and is particularly preferably an aliphatic hydrocarbon, more preferably a cyclic hydrocarbon solvent, and further preferably at least one selected from cyclohexane, cycloheptane, and methylcyclohexane.

[0231] When the above-mentioned combination of polymerizable monomer and hydrophobic solvent is used, the pressure resistance of the hollow particles is easily improved, so it is preferred. In particular, when a combination of a polymerizable monomer comprising an acrylic monomer and a hydrocarbon monomer and the above-mentioned preferred hydrophobic solvent is used, the uniformity of the shell is improved, thereby improving the pressure resistance of the hollow particles, so it is preferred.

[0232] In addition, the boiling point of the hydrophobic solvent is not particularly limited. From the viewpoint of easy removal in the solvent removal step described later, it is preferably 130°C or lower, and more preferably 100°C or lower. On the other hand, from the viewpoint of easy inclusion in the precursor particles, it is preferably 50°C or higher, and more preferably 60°C or higher.

[0233] In addition, when the hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent is preferably below the above-mentioned upper limit value, and the boiling point of the solvent with the lowest boiling point among the solvents contained in the mixed solvent is preferably above the above-mentioned lower limit value.

[0234] In addition, the hydrophobic solvent used in the production method of the present invention preferably has a relative dielectric constant of 2.0 or less at 20° C. The relative dielectric constant is one of the indicators indicating the polarity of a compound. It is believed that when the relative dielectric constant of the hydrophobic solvent is sufficiently small, for example, 2.0 or less, phase separation in the droplets of the monomer composition proceeds rapidly, and hollows are easily formed.

[0235] Examples of hydrophobic solvents having a relative dielectric constant of 2.0 or less at 20° C. are as follows. The values ​​in parentheses are relative dielectric constants.

[0236] Pentane (1.8), hexane (1.9), heptane (1.9), octane (1.9), cyclohexane (2.0).

[0237] Regarding the relative dielectric constant at 20° C., reference can be made to the values ​​and other technical information recorded in known literature (e.g., Chemical Society of Japan, "Basic Handbook of Chemistry", revised 4th edition, Maruzen Co., Ltd., issued on September 30, 1993, pages II-498 to II-503). As a method for measuring the relative dielectric constant at 20° C., for example, a relative dielectric constant test performed in accordance with 23 of JIS C2101:1999 and setting the measuring temperature to 20° C. can be cited.

[0238] The porosity of the hollow particles can be adjusted by changing the amount of the hydrophobic solvent in the mixed solution. In the polymerization step described later, the polymerization reaction is carried out in a state where the oil droplets containing the polymerizable monomers and the like contain the hydrophobic solvent, so there is a tendency that the porosity of the obtained hollow particles increases as the content of the hydrophobic solvent increases.

[0239] In the present invention, from the viewpoint of easily controlling the particle size of the hollow particles, easily improving the porosity while maintaining the strength of the hollow particles, and easily reducing the residual amount of the hydrophobic solvent in the particles, the content of the hydrophobic solvent in the mixed solution is preferably 50 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the polymerizable monomer. The content of the hydrophobic solvent in the mixed solution is more preferably 70 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the polymerizable monomer, and further preferably 90 parts by mass or more and 200 parts by mass or less.

[0240] (C) Polymerization initiator

[0241] In the production method of the present invention, the mixed solution preferably contains an oil-soluble polymerization initiator as a polymerization initiator. As a method for polymerizing droplets of the monomer composition after suspending the mixed solution, there are emulsion polymerization using a water-soluble polymerization initiator and suspension polymerization using an oil-soluble polymerization initiator. Suspension polymerization can be performed by using an oil-soluble polymerization initiator.

[0242] The oil-soluble polymerization initiator is not particularly limited as long as it is a lipophilic polymerization initiator having a solubility in water of 0.2% by mass or less, and examples thereof include organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethylacetate, and tert-butyl peroxypivalate; and azo compounds such as 2,2′-azobis(2,4-dimethylvaleronitrile), azobisisobutyronitrile, and 2,2′-azobis(4-methoxy-2,4-dimethylvaleronitrile).

[0243] The content of the polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and further preferably 1 to 5 parts by mass relative to 100 parts by mass of the polymerizable monomer in the mixed solution. When the content of the polymerization initiator is above the above lower limit, the polymerization reaction can be fully carried out, and when the content of the polymerization initiator is below the above upper limit, the possibility of the oil-soluble polymerization initiator remaining after the polymerization reaction is completed is small, and the possibility of carrying out unexpected side reactions is also small.

[0244] (D) Dispersion stabilizer

[0245] The dispersion stabilizer is an agent that disperses the droplets of the monomer composition in the aqueous medium in the suspension step. In the present invention, an inorganic dispersion stabilizer is preferably used as the dispersion stabilizer from the viewpoint of being able to narrow the particle size distribution of the obtained hollow particles by easily controlling the particle size of the droplets in the suspension and suppressing the decrease in the strength of the hollow particles by preventing the shell from becoming too thin.

[0246] Examples of the inorganic dispersion stabilizer include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; inorganic compounds such as metal hydroxides such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, and iron hydroxide. These inorganic dispersion stabilizers can be used alone or in combination of two or more.

[0247] Among the above-mentioned inorganic dispersion stabilizers, the above-mentioned sulfates, carbonates, phosphates, metal hydroxides and other poorly water-soluble metal salts are preferred, metal hydroxides are more preferred, and magnesium hydroxide is particularly preferred.

[0248] In the present invention, poorly soluble in water means that the solubility in 100 g of water is preferably 0.5 g or less.

[0249] In the present invention, it is particularly preferred to use the sparingly water-soluble inorganic dispersion stabilizer in a state where the sparingly water-soluble inorganic dispersion stabilizer is dispersed in an aqueous medium in the form of colloidal particles, that is, in a colloidal dispersion liquid containing the sparingly water-soluble inorganic dispersion stabilizer colloidal particles. This can not only narrow the particle size distribution of the droplets of the monomer composition, but also easily suppress the residual amount of the inorganic dispersion stabilizer in the obtained hollow particles to a low level by washing.

[0250] The colloidal dispersion containing the sparingly water-soluble inorganic dispersion stabilizer colloid particles can be prepared, for example, by reacting at least one selected from alkali metal hydroxides and alkaline earth metal hydroxides with a water-soluble polyvalent metal salt (excluding alkaline earth metal hydroxides) in an aqueous medium.

[0251] Examples of the alkali metal hydroxide salt include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Examples of the alkaline earth metal hydroxide salt include barium hydroxide, calcium hydroxide, etc.

[0252] As the water-soluble polyvalent metal salt, any polyvalent metal salt showing water solubility other than the compounds belonging to the above-mentioned alkaline earth metal hydroxide salts may be mentioned, for example: magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; zinc salts such as zinc chloride, zinc nitrate, and zinc acetate. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are particularly preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred. In addition, the water-soluble polyvalent metal salts can be used alone or in combination of two or more.

[0253] The method for reacting at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides with the above-mentioned water-soluble polyvalent metal salt in an aqueous medium is not particularly limited, and an example thereof includes mixing an aqueous solution of at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides with an aqueous solution of a water-soluble polyvalent metal salt.

[0254] The content of the dispersion stabilizer is not particularly limited, and is preferably 0.5 to 15 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomer and the hydrophobic solvent. When the content of the dispersion stabilizer is above the lower limit, the droplets of the monomer composition can be fully dispersed in the suspension without agglomerating. On the other hand, when the content of the dispersion stabilizer is below the upper limit, the viscosity of the suspension can be prevented from increasing during granulation, and the undesirable situation of clogging of the suspension in the granulator can be avoided.

[0255] The content of the dispersion stabilizer is preferably 0.5 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the aqueous medium.

[0256] (E) Water-based media

[0257] In the present invention, the aqueous medium refers to a medium selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent.

[0258] When a mixture of water and a hydrophilic solvent is used, it is important that the polarity of the mixture as a whole does not become too low from the viewpoint of forming droplets of the monomer composition. In this case, the mass ratio of water to the hydrophilic solvent (water:hydrophilic solvent) can be, for example, 99:1 to 50:50.

[0259] The hydrophilic solvent in the present invention is not particularly limited as long as it is fully miscible with water without phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO).

[0260] The content of the aqueous medium is not particularly limited. From the viewpoint of making the particle size and porosity of the hollow particles within the preferred range described below, the lower limit is preferably 200 parts by mass or more, more preferably 400 parts by mass or more, and further preferably 600 parts by mass or more, relative to 100 parts by mass of the polymerizable monomer contained in the mixed solution, and the upper limit is preferably 1000 parts by mass or less, and more preferably 800 parts by mass or less.

[0261] The mixed liquid may contain other materials different from the above-mentioned materials (A) to (E) within a range not impairing the effects of the present invention.

[0262] A mixed solution can be obtained by mixing the above-mentioned materials with other materials as required and stirring them appropriately. In the mixed solution, the oil phase containing the above-mentioned (A) polymerizable monomer, (B) hydrophobic solvent and (C) lipophilic materials such as polymerization initiator is dispersed in a water phase containing (D) dispersion stabilizer and (E) aqueous medium, etc., with a particle size of about several mm. The dispersion state of these materials in the mixed solution can be observed even with the naked eye depending on the type of materials.

[0263] In the mixed solution preparation step, the mixed solution can be obtained by simply mixing the above-mentioned materials with other materials as needed and stirring appropriately. From the viewpoint that the shell is easy to become uniform, it is preferred to separately prepare an oil phase containing a polymerizable monomer, a hydrophobic solvent and a polymerization initiator and an aqueous phase containing a dispersion stabilizer and an aqueous medium in advance, and mix them to prepare a mixed solution. In the present invention, a colloidal dispersion obtained by dispersing a sparingly water-soluble inorganic dispersion stabilizer in an aqueous medium in the form of colloidal particles can be preferably used as the aqueous phase.

[0264] By preparing the oil phase and the water phase separately in advance and then mixing them, hollow particles having a uniform composition of the shell portion can be produced, and the particle size of the hollow particles can also be easily controlled.

[0265] (2) Suspension process

[0266] The suspension step is a step of preparing a suspension in which droplets of a monomer composition containing a hydrophobic solvent are dispersed in an aqueous medium by suspending the mixed liquid.

[0267] The suspension method for forming the droplets of the monomer composition is not particularly limited, and a known suspension method can be used. Examples of the disperser used when preparing the suspension include horizontal or vertical pipeline dispersers such as Milder (product name) manufactured by Pacifico Machinery Co., Ltd., Cavitron (product name) manufactured by Eurotech Co., Ltd., and pipeline dispersers manufactured by Aika Co., Ltd. (e.g., DISPAX-REACTOR (registered trademark) DRS (product name)); emulsifying dispersers such as Homomixer Mark II series manufactured by Plemix Co., Ltd., etc.

[0268] In the suspension prepared in the suspension step, droplets of the monomer composition containing the lipophilic material and having a particle size of about 5 to 40 μm are uniformly dispersed in the aqueous medium. Such droplets of the monomer composition are not easily observed with the naked eye, but can be observed with a known observation device such as an optical microscope.

[0269] In the suspension step, phase separation occurs in the droplets of the monomer composition, so the hydrophobic solvent with low polarity tends to gather inside the droplets. As a result, in the obtained droplets, the hydrophobic solvent is distributed inside and the material other than the hydrophobic solvent is distributed around the droplets.

[0270] Figure 2 The diagram is a schematic diagram showing one embodiment of a suspension in the suspension process. Figure 2 The cross section of the droplet 8 of the monomer composition is schematically shown. Figure 2 This is only a schematic diagram, and the suspension in the present invention is not necessarily limited to Figure 2 Suspension shown. Figure 2 Part of the above Figure 1 corresponds to (2).

[0271] exist Figure 2 , a state where droplets 8 of a monomer composition and polymerizable monomers 4c dispersed in an aqueous medium 1 are dispersed in an aqueous medium 1 is shown. The droplets 8 are formed by surrounding an oil-soluble monomer composition 4 with a dispersion stabilizer 3 .

[0272] The monomer composition contains an oil-soluble polymerization initiator 5, a polymerizable monomer, and a hydrophobic solvent (neither of which are shown in the figure).

[0273] The droplets 8 are fine oil droplets containing the monomer composition 4, and the oil-soluble polymerization initiator 5 generates polymerization initiation radicals inside the fine oil droplets. Therefore, precursor particles having a target particle size can be produced without excessively growing the fine oil droplets.

[0274] In the suspension polymerization method using such an oil-soluble polymerization initiator, there is no chance for the polymerization initiator to contact the polymerizable monomer 4c dispersed in the aqueous medium 1. Therefore, by using an oil-soluble polymerization initiator, it is possible to suppress the by-production of unnecessary resin particles such as dense particles with a relatively small particle size other than the target resin particles having a hollow portion.

[0275] (3) Polymerization process

[0276] This step is a step of preparing a precursor composition containing precursor particles by subjecting the suspension obtained in the above-mentioned suspension step to a polymerization reaction, wherein the above-mentioned precursor particles have a hollow portion surrounded by a shell containing a resin and contain a hydrophobic solvent in the hollow portion. The precursor particles are formed by polymerization of polymerizable monomers contained in droplets of a monomer composition, and the shell of the precursor particles contains a polymer of the above-mentioned polymerizable monomer as a resin.

[0277] The polymerization method is not particularly limited, and for example, a batch method (intermittent method), a semi-continuous method, a continuous method, or the like can be adopted.

[0278] The polymerization temperature is preferably 40 to 90°C, more preferably 50 to 80°C.

[0279] Furthermore, the polymerization reaction time is preferably 1 to 48 hours, more preferably 4 to 36 hours.

[0280] In addition, in the manufacturing method of the present invention, in the polymerization step, a polymerizable monomer may be further added during the polymerization reaction of the polymerizable monomer in the suspension to carry out the polymerization reaction. By carrying out the polymerization reaction in two stages in the polymerization step, the pressure resistance of the hollow particles may be improved.

[0281] In the polymerization step, the shell portions of the droplets of the monomer composition containing the hydrophobic solvent are polymerized, and thus, as described above, hollow portions filled with the hydrophobic solvent are formed inside the obtained precursor particles.

[0282] (4) Solid-liquid separation process

[0283] This step is a step of obtaining a solid component containing precursor particles by solid-liquid separation of the precursor composition containing precursor particles obtained in the above-mentioned polymerization step.

[0284] The method for solid-liquid separation of the precursor composition is not particularly limited, and known methods can be used. As the method for solid-liquid separation, for example, centrifugation, filtration, static separation, etc. can be mentioned. Among these, centrifugation or filtration can be used. From the viewpoint of simplicity of operation, centrifugation can be used.

[0285] After the solid-liquid separation step and before the solvent removal step described below, an arbitrary step such as a pre-drying step may be performed. As the pre-drying step, for example, a step of pre-drying the solid component obtained after the solid-liquid separation step by a drying device such as a dryer or a drying tool such as a hand dryer may be mentioned.

[0286] (5) Solvent Removal Process

[0287] This step is a step of removing the hydrophobic solvent contained in the precursor particles obtained in the above-mentioned solid-liquid separation step.

[0288] By removing the hydrophobic solvent contained in the precursor particles in the gas, the hydrophobic solvent inside the precursor particles is replaced with air, thereby obtaining hollow particles filled with gas.

[0289] "In gas" in this process strictly refers to the environment of the outside of the precursor particles without liquid components at all and the environment of extremely small amounts of liquid components that only exist in the outside of the precursor particles and do not affect the removal of the hydrophobic solvent. "In gas" can also be said to be the state that the precursor particles are not present in the slurry, and can also be said to be the state that the precursor particles are present in the dry powder. That is, in this process, it is important to remove the hydrophobic solvent under the environment where the precursor particles are in direct contact with the gas outside.

[0290] The method for removing the hydrophobic solvent in the precursor particles in the gas is not particularly limited, and a known method can be adopted. Examples of the method include reduced pressure drying, heating drying, air flow drying, and a combination of these methods.

[0291] In particular, when a heat drying method is used, the heating temperature needs to be above the boiling point of the hydrophobic solvent and below the highest temperature at which the shell structure of the precursor particles does not collapse. Depending on the composition of the shell in the precursor particles and the type of the hydrophobic solvent, the heating temperature can be, for example, 50 to 200° C., 70 to 200° C., or 100 to 200° C.

[0292] By the drying operation in the gas, the hydrophobic solvent inside the precursor particles is replaced by the external gas, and as a result, hollow particles in which the hollow part is occupied by the gas can be obtained.

[0293] The dry atmosphere is not particularly limited and can be appropriately selected according to the purpose of the hollow particles. As the dry atmosphere, for example, air, oxygen, nitrogen, argon, etc. can be considered. In addition, after the hollow particles are temporarily filled with gas, by performing reduced pressure drying, hollow particles whose interior is temporarily vacuum can also be obtained.

[0294] As another method, the hydrophobic solvent contained in the precursor particles may be removed from the slurry containing the precursor particles and the aqueous medium without performing solid-liquid separation of the slurry-like precursor composition obtained in the polymerization step.

[0295] In this method, an inert gas is blown into the precursor composition at a temperature equal to or higher than the temperature obtained by subtracting 35° C. from the boiling point of the hydrophobic solvent, thereby removing the hydrophobic solvent included in the precursor particles.

[0296] Here, when the hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, the boiling point of the hydrophobic solvent in the solvent removal step refers to the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent, that is, the highest boiling point among the multiple boiling points.

[0297] From the viewpoint of reducing the residual amount of the hydrophobic solvent in the hollow particles, the temperature when the inert gas is blown into the precursor composition is preferably a temperature equal to or higher than the temperature obtained by subtracting 30°C from the boiling point of the hydrophobic solvent, and more preferably a temperature equal to or higher than the temperature obtained by subtracting 20°C from the boiling point of the hydrophobic solvent. In addition, the temperature during the blowing is usually set to a temperature equal to or higher than the polymerization temperature in the above-mentioned polymerization step. The temperature during the blowing is not particularly limited and can be set to 50°C or higher and 100°C or lower.

[0298] The inert gas to be blown in is not particularly limited, and examples thereof include nitrogen and argon.

[0299] The blowing conditions can be appropriately adjusted according to the type and amount of the hydrophobic solvent so as to remove the hydrophobic solvent contained in the precursor particles, and are not particularly limited. For example, the inert gas may be blown in at a rate of 1 to 3 L / min for 1 to 10 hours.

[0300] In this method, a slurry of hollow particles containing an aqueous medium can be obtained. The hollow particles obtained by solid-liquid separation of the slurry are dried to remove the aqueous medium contained in the hollow particles, thereby obtaining hollow particles in which the hollow part occupies a gas.

[0301] The following two methods are compared, namely, a method of removing the hydrophobic solvent in the precursor particles in a gas after solid-liquid separation of a slurry-like precursor composition, thereby obtaining hollow particles whose hollow parts are filled with gas, and a method of removing the hydrophobic solvent enclosed in the precursor particles in a slurry containing precursor particles and an aqueous medium, then performing solid-liquid separation and removing the aqueous medium in the hollow particles in a gas, thereby obtaining hollow particles whose hollow parts are filled with gas. The former method has the advantage that the hollow particles are not easily broken in the step of removing the hydrophobic solvent, and the latter method has the advantage that the residual amount of the hydrophobic solvent is reduced by bubbling with an inert gas.

[0302] In addition, as a method for removing the hydrophobic organic solvent contained in the precursor particles without performing solid-liquid separation on the slurry-like precursor composition obtained in the polymerization step after the polymerization step and before the solid-liquid separation step, for example, a method of distilling off the hydrophobic organic solvent contained in the precursor particles from the precursor composition under a specified pressure (under high pressure, under normal pressure, or under reduced pressure); a method of introducing an inert gas such as nitrogen, argon, helium, or water vapor into the precursor composition under a specified pressure (under high pressure, under normal pressure, or under reduced pressure) to distill off the hydrophobic organic solvent.

[0303] (6) Others

[0304] As steps other than the above-mentioned (1) to (5), for example, the following (6-a) cleaning step and the following (6-b) hollow portion re-replacement step may be added.

[0305] (6-a) Cleaning process

[0306] The cleaning step refers to a step of adding an acid or alkali to clean the precursor composition containing the precursor particles for the purpose of removing the dispersion stabilizer remaining in the precursor composition containing the precursor particles before the above-mentioned solvent removal step. When the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in acid, it is preferred to add an acid to the precursor composition containing the precursor particles for cleaning. On the other hand, when the dispersion stabilizer used is an inorganic compound soluble in alkali, it is preferred to add an alkali to the precursor composition containing the precursor particles for cleaning.

[0307] Furthermore, when an inorganic dispersion stabilizer soluble in an acid is used as the dispersion stabilizer, it is preferred to add an acid to the precursor composition containing the precursor particles to adjust the pH to preferably 6.5 or less, more preferably 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, and sulfuric acid is particularly preferred from the viewpoint of high removal efficiency of the dispersion stabilizer and small burden on the production equipment.

[0308] (6-b) Re-replacement step of hollow portion

[0309] The re-replacement process of the hollow part refers to the process of replacing the gas or liquid inside the hollow particle with other gas or liquid. By such replacement, the environment inside the hollow particle can be changed, or molecules can be selectively enclosed inside the hollow particle, or the chemical structure inside the hollow particle can be modified according to the application.

[0310] The hollow particles used in the present invention contain a polymer of the above-mentioned polymerizable monomer as a main component of the shell, and this polymer forms the skeleton of the shell of the hollow particles.

[0311] In the hollow particles of the present invention, from the viewpoint of improving pressure resistance, the above-mentioned polymer contained in the shell includes a cross-linking monomer unit. In all monomer units of 100 parts by mass of the above-mentioned polymer, the content of the cross-linking monomer unit is more than 50 parts by mass, preferably more than 60 parts by mass, more preferably more than 70 parts by mass, and more preferably more than 80 parts by mass. On the other hand, within the scope of not damaging the effect of the present invention, the above-mentioned polymer may also contain a non-cross-linking monomer unit, in which case, in all monomer units of 100 parts by mass of the above-mentioned polymer, the content of the cross-linking monomer unit may be, for example, less than 95 parts by mass, or less than 90 parts by mass.

[0312] In the hollow particles used in the present invention, from the viewpoint of improving pressure resistance, the above-mentioned polymer contained in the shell preferably contains a trifunctional or higher cross-linking monomer unit. In 100 parts by mass of all monomer units of the above-mentioned polymer, the lower limit of the content of the trifunctional or higher cross-linking monomer unit is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and the upper limit of the content of the trifunctional or higher cross-linking monomer unit is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 30 parts by mass or less.

[0313] In the hollow particles used in the present invention, from the viewpoint of improving pressure resistance, the above-mentioned polymer contained in the shell preferably contains a bifunctional cross-linking monomer unit and a trifunctional or higher cross-linking monomer unit. In the case where the above-mentioned polymer contains a bifunctional cross-linking monomer unit and a trifunctional or higher cross-linking monomer unit, in the total of 100 parts by mass of the bifunctional cross-linking monomer unit and the trifunctional or higher cross-linking monomer unit, the content of the trifunctional or higher cross-linking monomer unit is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 20 parts by mass or more, on the other hand, preferably 50 parts by mass or less, more preferably 40 parts by mass or less.

[0314] In the present invention, a crosslinkable monomer unit derived from a bifunctional crosslinkable monomer may be referred to as a "bifunctional crosslinkable monomer unit", and a crosslinkable monomer unit derived from a trifunctional or higher crosslinkable monomer may be referred to as a "trifunctional or higher crosslinkable monomer unit".

[0315] In addition, in the hollow particles used in the present invention, from the viewpoint of easily improving the uniformity of the shell, it is preferred that the above-mentioned polymer contained in the shell contains an acrylic acid-based monomer unit. The content of the acrylic acid-based monomer unit is not particularly limited, and is preferably 10 parts by mass or more, more preferably 20 parts by mass or more in 100% by mass of all monomer units.

[0316] Furthermore, in the hollow particles used in the present invention, the polymer contained in the shell preferably contains an acrylic monomer unit and a hydrocarbon monomer unit from the viewpoint of easily improving the uniformity of the shell and improving the pressure resistance.

[0317] The total content of acrylic acid monomer units and hydrocarbon monomer units in 100 parts by mass of all monomer units of the polymer is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 98 parts by mass or more, and further preferably 99 parts by mass or more.

[0318] In the case where the above-mentioned polymer contained in the shell contains acrylic acid monomer units and hydrocarbon monomer units, from the viewpoint of improving the pressure resistance of the hollow particles, the lower limit of the content of the hydrocarbon monomer units in 100 parts by mass of the total of the acrylic acid monomer units and the hydrocarbon monomer units is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and further preferably 30 parts by mass or more, and the upper limit of the content of the hydrocarbon monomer units is preferably 90 parts by mass or less, and more preferably 80 parts by mass or less.

[0319] In the hollow particles used in the present invention, the content of the polymer synthesized from the above-mentioned polymerizable monomer is preferably 96% by mass or more, more preferably 97% by mass or more, in the total solid content of 100% by mass of the shell. By making the content of the above-mentioned polymer above the above-mentioned lower limit, the reduction in the pressure resistance of the hollow particles can be suppressed. That is, from the viewpoint of suppressing the reduction in the pressure resistance of the hollow particles, in the total solid content of 100% by mass of the shell, the content of the components other than the above-mentioned polymer is preferably 4% by mass or less, more preferably 3% by mass or less.

[0320] In addition, as components other than the above-mentioned polymer contained in the hollow particles used in the present invention, for example, polymerizable monomers remaining in an unreacted state, polymers different from the polymers of the above-mentioned polymerizable monomers, decomposition products of polymerization initiators, low molecular weight compounds contained as impurities in the raw materials of polymerizable monomers, etc. Among these, substances with low boiling points (e.g., boiling points below 200° C.) are usually removed during the production process of hollow particles, but substances with high boiling points (e.g., boiling points above 250° C.) are sometimes not removed and remain.

[0321] [Plasticizer]

[0322] In order to make the storage modulus G' of the hollow particle-containing elastomer composition measured under specified conditions below a specific value, a plasticizer is added to the hollow particle-containing elastomer composition of the present invention as needed. As the plasticizer, substances generally used as plasticizers in applications such as vehicle-mounted materials, conventional plastics, and rubber products, or substances that impart flexibility can be used.

[0323] As plasticizers, petroleum-based softeners such as process oil, lubricating oil, paraffin, liquid paraffin, petroleum asphalt, and vaseline; coal tar-based softeners such as coal tar and coal tar pitch; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, and coconut oil; tall oil; waxes such as beeswax, carnauba wax, and lanolin; fatty acids and fatty acid salts such as ricinoleic acid, palmitic acid, barium stearate, calcium stearate, and zinc laurate; synthetic polymers such as petroleum resins, random polypropylene, and coumarone indene resins; ester plasticizers such as dioctyl phthalate, dioctyl adipate, and dioctyl sebacate; carbonate plasticizers such as diisododecyl carbonate; other microcrystalline waxes, rubber substitutes (ointments), liquid polybutadiene, modified liquid polybutadiene, liquid mercaptan, and hydrocarbon-based synthetic lubricating oils can be used alone or in combination of two or more.

[0324] From the viewpoint of preventing the plasticizer from bleeding out of the molded body manufactured using the hollow particle-containing elastomer composition of the present invention, it is preferred that the plasticizer include a polymer selected from polymers having reactive sites that are bonded to the base elastomer and having a weight average molecular weight of greater than 1,000 and less than 100,000 (hereinafter sometimes referred to as a "reactive site-containing plasticizer") as the plasticizer.

[0325] The above-mentioned plasticizer containing reactive sites not only acts as a plasticizer during melt-kneading of the elastomer composition and its raw material mixture, but also combines with the molecules of the base elastomer during melt-kneading of the elastomer composition and its raw material mixture or when the elastomer composition is used to manufacture a molded body. The plasticizer containing reactive sites itself is integrated with the matrix in the elastomer composition and its raw material mixture, thereby preventing the plasticizer from seeping out.

[0326] In particular, when a large amount of plasticizer is used, the plasticizer is likely to bleed out. Therefore, when a large amount of plasticizer is added in order to sufficiently reduce the storage modulus G' of the elastomer composition and its raw material mixture during melt kneading, it is preferred to use the above-mentioned reactive site-containing plasticizer.

[0327] The polymer skeleton serving as the main part in the molecular structure of the plasticizer containing reactive sites may have any chemical structure as long as it has appropriate compatibility, softening properties or fluidity during melt-kneading of the elastomer composition and its raw material mixture and can function as a plasticizer. For example, a skeleton having a hydrocarbon polymer structure which may contain heteroatoms such as oxygen, nitrogen, silicon, etc. in the main chain or side chain may be exemplified.

[0328] The reactive site that binds to the base elastomer refers to a chemical structure that has the function of forming a chemical, physical or physicochemical bond with the reactive site existing on the base elastomer. In the case where the reactive site-containing plasticizer has two or more reactive sites that bind to the base elastomer in one molecule, the reactive site-containing plasticizer forms a crosslinked structure via the plasticizer between two base elastomer molecules, and the plasticizer and the base are highly integrated, so the effect of preventing the plasticizer from seeping out is high.

[0329] When the plasticizer containing reactive sites has two or more reactive sites in one molecule and the reactive sites can also combine with hollow particles, the plasticizer containing reactive sites forms a cross-linked structure not only between two substrate elastomer molecules, but also between the substrate elastomer molecules and the hollow particles and between the two hollow particles, thereby having a higher effect in preventing the plasticizer from seeping out.

[0330] When the number of reactive sites per molecule of the reactive site-containing plasticizer is too large, the matrix in the elastomer composition and the raw material mixture thereof is excessively networked, and the melt fluidity is deteriorated. Therefore, from the viewpoint of making the storage modulus G′ of the hollow particle-containing elastomer composition and the raw material mixture of the present invention measured under predetermined conditions be a certain value or less, the number of reactive sites per molecule of the reactive site-containing plasticizer is preferably 2 to 10,000.

[0331] From the viewpoint of imparting sufficient plasticization, the plasticizer containing a reactive site is preferably liquid at at least one point within the range of room temperature (20°C±15°C), more preferably liquid at at least one point within the range of 10°C to 30°C, and more preferably liquid at least one point within the range of 20°C to 25°C.

[0332] From the same viewpoint of imparting sufficient plasticization, the plasticizer containing a reactive site preferably has a glass transition temperature of -10°C or lower, more preferably -120°C to -20°C.

[0333] When the base elastomer has olefinic double bonds such as butadiene rubber and styrene butadiene rubber, the olefinic double bonds on the base elastomer can serve as reactive sites, and thus the olefinic double bonds can be utilized as reactive sites for bonding with the base elastomer.

[0334] Furthermore, when the shell of the hollow particle is synthesized from a monomer having an ethylenic double bond or a crosslinking monomer and unreacted ethylenic double bonds remain in the shell, the ethylenic double bonds on the shell can become reactive sites, and thus the ethylenic double bonds can be utilized as reactive sites for bonding with the hollow particle.

[0335] Therefore, when an elastomer selected from butadiene rubber and styrene butadiene rubber is used as the base elastomer, a polymer having an olefinic double bond can be used as the reactive site-containing plasticizer.

[0336] As the reactive site-containing plasticizer selected from polymers having ethylenic double bonds and a weight average molecular weight of 1,000 to 100,000, it is preferred to use a diene rubber that is liquid at room temperature.

[0337] Examples of the diene rubber that is liquid at room temperature include: unmodified liquid polybutadiene rubber; modified liquid polybutadiene rubbers such as acrylate-modified liquid polybutadiene; liquid styrene-butadiene rubber; unmodified liquid polyisoprene rubber; modified liquid polyisoprene rubbers such as hydroxyl-terminated liquid polyisoprene rubber, etc. Among these, unmodified liquid polybutadiene rubber and modified liquid polybutadiene rubber are preferred.

[0338] Furthermore, as the reactive site-containing plasticizer selected from polymers having olefinic double bonds and a weight average molecular weight of 1000 to 100000, polyolefins having terminal double bonds are also preferably used. Examples of polyolefins having terminal double bonds include polypropylenes having terminal double bonds.

[0339] The content of the plasticizer in the elastomer composition is not particularly limited, but is usually 35 to 100 parts by mass, preferably 45 to 90 parts by mass, based on 100 parts by mass of the base elastomer.

[0340] When the above-mentioned plasticizer containing reactive sites is used, if the content of the plasticizer containing reactive sites is within a suitable range, the effect of imparting plasticity is more dominant than the elasticity increase of the composition brought about by the formation of the linking structure, and therefore, while fully functioning as a plasticizer, it also prevents exudation. However, when the content of the plasticizer containing reactive sites is too little, the elasticity increase of the composition brought about by the formation of the linking structure is dominant, and therefore, the effect of imparting plasticity is hindered. In addition, when the content of the plasticizer containing reactive sites is excessive, the effect of imparting plasticity is enhanced, but the formation of the linking structure reaches saturation, and the plasticizer still in a free state is easy to ooze out.

[0341] For the above reasons, when the reactive site-containing plasticizer is used alone, the content of the reactive site-containing plasticizer is preferably 65 to 90 parts by mass, more preferably 70 to 85 parts by mass, and even more preferably 70 to 80 parts by mass based on 100 parts by mass of the base elastomer.

[0342] When a plasticizer having no reactive sites and a plasticizer having reactive sites are used in combination, the proportion of the plasticizer having reactive sites is preferably 5 to 35% by mass, more preferably 10 to 30% by mass, based on the total amount of the plasticizers.

[0343] [Vulcanization cross-linking agent]

[0344] In order to crosslink the base elastomer, the hollow particle-containing elastomer composition of the present invention adds a vulcanization crosslinking agent as needed. Examples of the vulcanization crosslinking agent include sulfur such as powdered sulfur, precipitated sulfur, colloidal sulfur, and insoluble sulfur; inorganic vulcanizing agents such as sulfur chloride, selenium, and tellurium; sulfur-containing organic compounds such as dithiomorpholine, disulfide alkylphenols, disulfide thiurams, and dithiocarbamates; organic peroxides such as 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, di-tert-butyl peroxide, dicumyl peroxide, tert-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 1,3-bis(tert-butylperoxyisopropyl)benzene, etc. These vulcanization crosslinking agents can be used alone or in combination of two or more. The amount of the vulcanization crosslinking agent can be appropriately selected according to its type, and is usually in the range of 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the base elastomer. In addition, a vulcanization accelerator or a vulcanization accelerating auxiliary can also be used in combination as needed.

[0345] [Other ingredients]

[0346] The hollow particle-containing elastomer composition of the present invention may contain conventionally known additives such as reinforcing agents, fillers, vulcanization accelerators, softeners, processing aids, antioxidants, ultraviolet absorbers, foaming agents, foaming aids, lubricants, pigments, colorants, dispersants, flame retardants, etc., as needed, without impairing the purpose of the present invention.

[0347] The reinforcing agent has the effect of improving the mechanical properties of the elastomer such as tensile strength, tear strength, and abrasion resistance. As such reinforcing agents, specifically, carbon blacks such as SRF, GPF, FEF, HAF, ISAF, SAF, FT, and MT, these carbon blacks surface-treated with silane coupling agents, fine powder silicic acid, silicon dioxide, etc. can be cited. These reinforcing agents can be used alone or in combination of two or more. The amount of the reinforcing agent is not particularly limited, and is usually 230 parts by mass or less relative to 100 parts by mass of the base elastomer.

[0348] As fillers, inorganic fillers such as calcium carbonate, light calcium carbonate, heavy calcium carbonate, magnesium carbonate, talc, clay, glass beads, glass balloons, etc. can be cited; organic fillers such as high styrene resins, coumarone indene resins, phenolic resins, lignin, modified melamine resins, and petroleum resins are particularly preferably used. Inorganic fillers can be used alone or in combination of two or more. The amount of filler is not particularly limited, and is usually 30 to 200 parts by mass relative to 100 parts by mass of the base elastomer.

[0349] Specific examples of the vulcanization accelerator include aldehyde amines such as hexamethylenetetramine; guanidines such as diphenylguanidine, di(o-tolyl)guanidine, and o-tolylbiguanide; thioureas such as diphenylthiourea, di(o-tolyl)thiourea, N,N′-diethylthiourea, and dilaurylthiourea; thiazoles such as mercaptobenzothiazole, dibenzothiazole disulfide, and N,N′-di(ethylthiocarbamoylthio)benzothiazole; sulfonamides such as N-tert-butyl-2-benzothiazolesulfenamide; thiurams such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetrabutylthiuram disulfide; carbamates such as zinc dimethylthiocarbamate, sodium dimethyldithiocarbamate, copper dimethyldithiocarbamate, tellurium dimethylthiocarbamate, and iron dimethylthiocarbamate; xanthates such as zinc butylthioxanthate, and the like.

[0350] These vulcanization accelerators can be used alone or in combination of two or more. The amount of the vulcanization accelerator is generally in the range of 0.1 to 20 parts by mass, preferably in the range of 0.2 to 10 parts by mass, relative to 100 parts by mass of the base elastomer. Specifically, metal oxides such as magnesium oxide and zinc white; organic acids (salts) such as stearic acid, oleic acid, and zinc stearate, etc., are mentioned, and zinc white and stearic acid are particularly preferred. These vulcanization accelerators can be used alone or in combination of two or more. The amount of the vulcanization accelerator is generally in the range of 0.5 to 20 parts by mass, relative to 100 parts by mass of the base elastomer.

[0351] As softeners, there can be mentioned: petroleum softeners such as process oil, lubricating oil, paraffin, liquid paraffin, petroleum asphalt, vaseline, etc.; coal tar softeners such as coal tar and coal tar pitch; fatty oil softeners such as castor oil, linseed oil, rapeseed oil, coconut oil, etc.; tall oil; rubber substitutes; waxes such as beeswax, carnauba wax, lanolin, etc.; fatty acids and fatty acid salts such as ricinoleic acid, palmitic acid, barium stearate, calcium stearate, and zinc laurate; synthetic polymers such as petroleum resins, random polypropylene, coumarone indene resins, etc.; ester plasticizers such as dioctyl phthalate, dioctyl adipate, dioctyl sebacate, etc.; carbonate plasticizers such as diisododecyl carbonate, etc.; other microcrystalline waxes, rubber substitutes (ointments), liquid polybutadiene, modified liquid polybutadiene, liquid mercaptan, hydrocarbon synthetic lubricating oils, etc. Among them, petroleum softeners are preferred, and process oils are particularly preferred. The amount of the softener to be added is not particularly limited, but is usually 10 to 200 parts by mass based on 100 parts by mass of the base elastomer.

[0352] As processing aids, there are: higher fatty acids such as ricinoleic acid, stearic acid, palmitic acid, and lauric acid; salts of higher fatty acids such as barium stearate, zinc stearate, and calcium stearate; esters of higher fatty acids such as ricinoleic acid, stearic acid, palmitic acid, and lauric acid, etc. As antioxidants, there are, for example, amine-based, hindered phenol-based, and sulfur-based antioxidants.

[0353] Examples of lubricants include compounds or mixtures of hydrocarbons such as liquid paraffin, fatty acids such as stearic acid, fatty acid amides such as stearic acid amide, esters such as butyl stearate, alcohols such as stearyl alcohol, and metal soaps.

[0354] Examples of the pigment include inorganic pigments such as titanium dioxide, zinc oxide, ultramarine, red iron oxide, lithopone, lead, cadmium, iron, cobalt, aluminum, hydrochloride, and nitrate; azo pigments, phthalocyanine pigments, quinacridone pigments, quinacridonequinone pigments, dioxane pigments, and the like. Organic pigments include oxazine pigments, anthrapyrimidine pigments, anthranthrone pigments, indanthrone pigments, flavanthrone pigments, perylene pigments, pyrene pigments, diketopyrrolopyrrole pigments, quinonaphthalon pigments, anthraquinone pigments, thioindigo pigments, benzimidazolone pigments, isoindoline pigments, carbon black, and the like.

[0355] [Method for producing hollow particle-containing elastomer composition]

[0356] The preparation method of the hollow particle-containing elastomer composition of the present invention is not particularly limited. Usually, at a temperature at which the base elastomer softens, a raw material mixture containing a base elastomer and hollow particles, and other components such as a plasticizer and a vulcanization crosslinking agent as required is pre-mixed, thereby homogenizing the ingredients, and then performing finishing mixing such as roller mixing with a high shear force, thereby further homogenizing and miniaturizing the ingredients to obtain a hollow particle-containing elastomer composition. In order to prevent the raw material mixture from being cross-linked by a vulcanization crosslinking agent during pre-mixing, a vulcanization crosslinking agent may also be added in the process of finishing mixing after pre-mixing. Furthermore, hollow particles may also be added in the process of finishing mixing.

[0357] In the present invention, in order to reduce the breakage of the hollow particles during the kneading stage of the raw material mixture of the hollow particle-containing elastomer composition, it is preferable to carry out the following steps:

[0358] A raw material mixture comprising at least a base elastomer and hollow particles is prepared, wherein the hollow particles have a shell comprising a resin and a hollow portion surrounded by the shell, the shell comprising a polymer comprising 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin, and the raw material mixture has a storage modulus G′ of 2.5 MPa or less at 60° C. obtained by dynamic viscoelasticity measurement after homogenization of the compounded components;

[0359] Using a closed-type mixer, pre-kneading the raw material mixture at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less;

[0360] Immediately after pre-mixing, or after preheating to a temperature at which the storage modulus G' obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less, the raw material mixture is kneaded at a temperature at which the storage modulus G' obtained by the dynamic viscoelasticity measurement after the above-mentioned homogenization treatment becomes 2.5 MPa or less. In addition, in order to mix the components uniformly, the above-mentioned kneading process (finishing kneading process) is preferably carried out by roll kneading.

[0361] In the above-mentioned production method, "kneading at a kneading temperature of 60° C. or higher" means that the set temperature of the kneading device is set to 60° C. or higher. Similarly, "kneading at a temperature of A° C.," "setting the kneading temperature to A° C.," "preheating at a temperature of A° C.," or "setting the molding temperature to A° C." means that the temperature of a kneading device, a heating device, a molding device, etc. is set to the value (A).

[0362] In the above-mentioned manufacturing method, the following hollow particles are used, i.e., hollow particles whose strength is improved by virtue of a shell composed of a resin containing a polymer with a high content ratio of cross-linkable monomer units, and whose strength does not decrease due to the cross-linked structure even in a high-temperature environment. Furthermore, the storage modulus G' of the raw material mixture containing the base elastomer and the hollow particles at 60°C is made less than 2.5 MPa, and pre-mixing and finishing mixing are carried out at a temperature at which the storage modulus G' of the raw material mixture is less than 2.5 MPa, thereby, the loads such as internal pressure and shear force applied to the hollow particles inside the raw material mixture during finishing mixing are suppressed to a low level.

[0363] Therefore, according to the production method of the present invention, the hollow particles are not easily broken in the kneading process, the residual porosity is stable, and the properties or functions imparted by the hollow particles are not easily damaged. Therefore, a hollow particle-containing elastomer composition having excellent properties or functions can be obtained.

[0364] Furthermore, according to the above-mentioned production method, even if the raw material mixture is repeatedly kneaded, the hollow particles existing in the raw material mixture can still maintain the initial porosity, and the effect of the hollow particles is not easily lost. Therefore, the elastomer composition recovered from the molding device can be reused as the raw material mixture as long as it is before the elastomer composition is crosslinked (vulcanized).

[0365] In order to implement the above method, a formulation is previously determined in which the storage modulus G′ at 60° C. obtained by dynamic viscoelasticity measurement of the raw material mixture is 2.5 MPa or less.

[0366] The dynamic viscoelasticity measurement of the raw material mixture can be carried out by the same method as the dynamic viscoelasticity measurement of the hollow particle elastomer composition, but since the raw material mixture is a composition before kneading and the uniformity of the ingredients is insufficient, if the dynamic viscoelasticity measurement is directly carried out, the measured values ​​vary greatly or cannot be measured. Therefore, the dynamic viscoelasticity measurement of the raw material mixture needs to be carried out after the distribution of the ingredients contained in the raw material mixture is homogenized to obtain a stable measured value. The conditions for the homogenization treatment are not particularly limited, and for example, the homogenization treatment can be carried out under the following conditions.

[0367] [Homogenization treatment]

[0368] The mixture containing at least the base elastic body and the hollow particles was kneaded at a kneading temperature of 100° C. and a kneading element rotation speed of 50 rpm using an internal kneading machine to be homogenized.

[0369] In addition, when dynamic viscoelasticity measurement is performed to determine a raw material mixture whose storage modulus at 60°C is 2.5 MPa or less, as long as the ease of crushing of the hollow particles in the manufacturing stage of the hollow particle-containing elastomer composition can be appropriately evaluated, a simple measurement can be performed using a simulated raw material mixture that does not contain a part of the components contained in the hollow particle-containing elastomer composition within a range that has a small impact on the change in the storage modulus at 60°C.

[0370] For example, the vulcanization crosslinking agent of the hollow particle-containing elastomer composition generally has little effect on the change in storage modulus at 60°C within the range of the conventional usage of the vulcanization crosslinking agent, so a simulated mixture containing no vulcanization crosslinking agent can be used as a sample for dynamic viscoelasticity measurement.

[0371] Generally, in order to uniformly knead a composition containing a base elastic body and hollow particles and, if necessary, other components such as a plasticizer and a vulcanization crosslinking agent, it is desirable to apply a high shear force such as roll kneading. However, high shear force tends to break the hollow particles.

[0372] In the present invention, the specific raw material mixture is pre-kneaded using a closed mixer at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less, and then, immediately or after pre-kneading, preheated to a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less, and then finished kneaded at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less. Thus, even if kneading with a high shear force such as roll kneading is performed, the load applied to the hollow particles will not become too large, and thus, a uniformly mixed elastomer composition can be produced while avoiding the breakage of the hollow particles.

[0373] In the present invention, the closed mixer used in the pre-mixing and the above-mentioned homogenization treatment refers to a chamber having a center portion for accommodating the rubber material to be processed, two rotors (stirring members) are arranged in the chamber, and the chamber has a structure for mixing the rubber entering between the two rotors by grinding it. The rotor is a member having blades (knife blades) mounted on a roller-shaped rotating shaft in order to uniformly mix the entire material without dead corners, and the rubber as the material is mixed in the chamber while being subjected to the shear force of the rotor.

[0374] As the closed-type kneading machine, for example, a kneader or a Banbury mixer can be used. More specifically, as the kneading machine, there can be mentioned the product name: Plasti-Corder Lab-Station (manufactured by Brabender), the product name: MS type pressure kneader (manufactured by Moriyama Co., Ltd.), and as the Banbury mixer, there can be mentioned the product name: MIXTRON BB MIXER (manufactured by Kobe Steel, Ltd.).

[0375] As a kneading machine used for finishing kneading, for example, a twin-roll kneading machine can be used, and more specifically, a product name: Roll Kneading Machine DY6-15 (manufactured by Daihan Co., Ltd.) can be cited.

[0376] The internal kneader used for premixing and the internal kneader used for homogenization treatment do not need to be devices with completely the same structure. However, from the viewpoint of predicting the behavior of the viscoelastic properties of the raw material mixture in the stage of premixing the raw material mixture as accurately as possible based on the viscoelastic properties of the raw material mixture measured in the stage of determining the formulation of the raw material mixture, it is preferred to use an internal kneader having the same device structure in the stage of premixing and the stage of homogenization treatment.

[0377] As an example, kneading can be performed by the following method. First, a closed mixer such as a kneader or a Banbury mixer having a weaker shear force than roll kneading is used, the kneading temperature is set to 100° C., and after the temperature of the closed mixer is stabilized, the base elastomer is added, and then, while the rotor of the closed mixer is rotated at a speed of 30 to 100 rpm, the hollow particles, the plasticizer, the vulcanization crosslinking agent and other components are added in an arbitrary order, thereby performing pre-kneading.

[0378] Next, the kneading temperature of the roll kneader is set to 60° C. or higher, and after the temperature of the roll kneader is stabilized, the pre-kneaded raw material mixture is immediately put into the roll kneader for roll kneading, thereby obtaining the hollow particle-containing elastomer composition of the present invention. By immediately putting the pre-kneaded raw material mixture from the closed kneader into the roll kneader, it is possible to prevent the temperature of the raw material mixture from decreasing during the process of transferring it from the pre-kneading step to the finishing kneading step, the melt fluidity thereof from decreasing, and the increase in the breakage of the hollow particles during the finishing kneading.

[0379] Here, the "immediately" in "immediately charged from the internal kneading mill into the roll kneading mill" means that the time required for transferring the raw material mixture from the preliminary kneading step to the finishing kneading step is short enough to suppress the increase in the breakage of the hollow particles during the finishing kneading to a range that can be ignored in practical use.

[0380] More specifically, the difference (unit: %) between the porosity of an elastomer molded body made from the pre-mixed raw material mixture measured according to the method for measuring the porosity residual rate of a hollow particle-containing elastomer molded body described later and the porosity of an elastomer made from the finally obtained hollow particle-containing elastomer composition measured using the same method is preferably 10% or less, and more preferably 5% or less.

[0381] Furthermore, specifically, when the time required to start finish kneading immediately after preliminary kneading without preheating is shown in time units, finish kneading of the raw material mixture is preferably started within 10 minutes, more preferably within 5 minutes after preliminary kneading.

[0382] Due to process problems, when the temperature of the raw material mixture becomes lower than 60°C when the raw material mixture is taken out of the pre-mixing device and transferred to the finishing mixing device, in order to maintain the temperature of the raw material mixture at a temperature at which the storage modulus G' of the raw material mixture becomes less than 2.5 MPa, it is preferred to preheat the raw material mixture at a preheating temperature set to above 60°C for an appropriate time, for example, about 1 hour, using a heating device such as an oven, and after preheating, put it into the finishing mixing device to start mixing.

[0383] In order to prevent the raw material mixture from being crosslinked by the vulcanization crosslinking agent during the pre-kneading process, a vulcanization crosslinking agent may be added in the roll kneading step after the pre-kneading. Furthermore, hollow particles may be added in the roll kneading step.

[0384] In order to prevent the raw material mixture from being crosslinked by the vulcanization crosslinking agent, it is preferred that the kneading be performed at a kneading temperature of 100° C. or lower in both the pre-kneading and the roll kneading.

[0385] The hollow particle-containing elastomer composition obtained as described above can be made into a product having any form of molding material. For example, the molten hollow particle-containing elastomer composition can be formed into a long sheet, a block, a filler, etc., or can be secondary processed into a long sheet wound into a roll, a long sheet cut into strips of a predetermined length, etc.

[0386] [Method for producing hollow particle-containing elastomer molded body]

[0387] The method for producing a molded article using the hollow particle-containing elastomer composition of the present invention is not particularly limited, but preferably includes a step of kneading the hollow particle-containing elastomer composition at a molding temperature of 60° C. or higher.

[0388] In general, when an elastomer molded body is produced using a molding elastomer composition, the elastomer composition is kneaded into a molten state having uniform components, and then subjected to any molding method such as extrusion molding, compression molding, extrusion lamination, etc. By using the hollow particle-containing elastomer composition of the present invention and molding at a molding temperature of 60° C. or higher, the storage modulus G′ of the hollow particle-containing elastomer composition during molding can be set to 2.5 MPa or less, and the load such as external pressure and shear force applied to the hollow particles will not become too large, so that the elastomer molded body can be produced while avoiding the crushing of the hollow particles.

[0389] The hollow particle-containing elastomer molded body obtained in the present invention can have a residual porosity of 80% or more, preferably 90% or more, more preferably 95% or more, and even more preferably 100%, as measured by the following test method.

[0390] [Method for measuring the residual porosity of hollow particle-containing elastomer molded body]

[0391] The hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to produce a sheet-shaped hollow particle-containing elastomer molded body.

[0392] The specific gravity of the obtained elastomer molded body was measured, and the porosity residual rate of the hollow particles in the elastomer molded body was calculated according to the following formula (D).

[0393] The following formula (D) is the same as the formula (D) for calculating the residual porosity in the above-mentioned compression test method performed to evaluate the crushing difficulty of hollow particles.

[0394] .

[0395] a: specific gravity of the compact after pressing,

[0396] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value),

[0397] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0398] Example

[0399] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are based on mass unless otherwise specified.

[0400] [Preparation of hollow particles]

[0401] [Production Example 1 (Hollow Particles A)]

[0402] (1) Mixed solution preparation process

[0403] First, mix the following materials to prepare an oil phase.

[0404] Cross-linking monomer: 25 parts of ethylene glycol dimethacrylate;

[0405] Crosslinking monomer: 30 parts of trimethylolpropane trimethacrylate;

[0406] Crosslinking monomer: 45 parts of divinylbenzene;

[0407] Oil-soluble polymerization initiator: 3 parts of 2,2′-azobis(2,4-dimethylvaleronitrile);

[0408] Hydrophobic solvent: 160 parts of hexane.

[0409] On the other hand, in a stirring tank, at room temperature, to an aqueous solution obtained by dissolving 17.1 parts of magnesium chloride (water-soluble multivalent metal salt) in 494 parts of ion exchange water, an aqueous solution obtained by dissolving 12.1 parts of sodium hydroxide (alkali metal hydroxide) in 121 parts of ion exchange water was slowly added while stirring to prepare a magnesium hydroxide colloid (metal hydroxide colloid that is sparingly soluble in water) dispersion (4 parts of magnesium hydroxide) to form an aqueous phase.

[0410] A mixed solution is prepared by mixing the obtained aqueous phase with the oil phase.

[0411] (2) Suspension process

[0412] The mixed solution obtained in the mixed solution preparation step was suspended by stirring at 4000 rpm for 1 minute using a disperser (manufactured by Plemix Co., Ltd., product name: Homomixer) to prepare a suspension in which droplets of the monomer composition containing a hydrophobic solvent were dispersed in water.

[0413] (3) Polymerization process

[0414] The suspension obtained in the above suspension step was stirred under a nitrogen atmosphere at a temperature of 65° C. for 1 hour and 30 minutes to perform a polymerization reaction, thereby obtaining a precursor composition including precursor particles enclosing a hydrophobic solvent.

[0415] (4) Cleaning process and solid-liquid separation process

[0416] The precursor composition was washed with dilute sulfuric acid (25°C, 10 minutes) to a pH of 5.5 or less. Then, after separating the water by filtration, 200 parts of ion exchange water were added again for re-slurrying, and the water washing treatment (washing, filtration, dehydration) was repeated several times at room temperature (25°C), and filtered to separate to obtain a solid component. The obtained solid component was dried at a temperature of 40°C in a dryer to obtain precursor particles containing a hydrophobic solvent.

[0417] (5) Solvent Removal Process

[0418] The precursor particles obtained in the solid-liquid separation step were heated at 200° C. in a nitrogen atmosphere for 12 hours using a vacuum dryer to remove the hydrophobic solvent contained in the particles, thereby obtaining hollow particles A. The obtained hollow particles were confirmed to be spherical and have a hollow portion based on the results of observation with a scanning electron microscope and the porosity value.

[0419] [Production Example 2 (Hollow Particles B)]

[0420] In Production Example 1, hollow particles of Production Example 2 (hollow particles B) were obtained by the same procedure as in Production Example 1 except that the formulation of the oil phase was changed as follows in the above-mentioned "(1) Mixed solution preparation step".

[0421] Cross-linking monomer: ethylene glycol dimethacrylate 70 parts;

[0422] Crosslinking monomer: 30 parts of trimethylolpropane trimethacrylate;

[0423] Oil-soluble polymerization initiator: 3 parts of 2,2′-azobis(2,4-dimethylvaleronitrile);

[0424] Hydrophobic solvent: 48 parts of cyclohexane;

[0425] Hydrophobic solvent: 112 parts of toluene.

[0426] The obtained hollow particles were confirmed to be spherical and have a hollow portion based on the results of observation with a scanning electron microscope and the value of the porosity.

[0427] [Evaluation of physical properties of hollow particles]

[0428] The following physical property evaluations were performed on the hollow particles obtained in each Production Example.

[0429] 1. Volume average particle size of hollow particles

[0430] The volume average particle size of the hollow particles was measured using a particle size distribution analyzer (Beckman Coulter, product name: Multisizer 4e) under the following measurement conditions: pore size: 50 μm, dispersion medium: Isoton II (product name), concentration: 10%, and number of particles to be measured: 100,000.

[0431] Specifically, 0.2 g of a particle sample was placed in a beaker, and an aqueous surfactant solution (manufactured by Fujifilm Corporation, product name: DRIWEL) was added thereto as a dispersant. 2 ml of a dispersion medium was further added thereto to wet the particles, and then 10 ml of a dispersion medium was added thereto, and the particles were dispersed for 1 minute using an ultrasonic disperser, and then measured using the above-mentioned particle size distribution measuring instrument.

[0432] 2. Density and porosity of hollow particles

[0433] 2-1. Determination of apparent density of hollow particles

[0434] First, in a volume of 100cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow particles filled was accurately weighed. Next, isopropyl alcohol was accurately filled to the mark in the volumetric flask filled with the hollow particles, while being careful not to mix in bubbles. The mass of isopropyl alcohol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm 3 ).

[0435] 2-2. Determination of true density of hollow particles

[0436] The hollow particles were crushed in advance and then filled with a 100cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed.

[0437] Then, isopropyl alcohol was added to the volumetric flask in the same manner as in the above-mentioned measurement of apparent density, the mass of isopropyl alcohol was accurately weighed, and the true density D0 (g / cm 3 ).

[0438] 2-3. Calculation of porosity

[0439] The porosity of the hollow particles is calculated based on the above formula (III) from the apparent density D1 and the true density D0 of the hollow particles.

[0440] 3. Residual porosity of hollow particles

[0441] The residual porosity of the hollow particles was measured by the following compression test method.

[0442] [Compression test method]

[0443] A mixture of polypropylene resin (manufactured by Japan Polypropylene Co., Ltd., trade name: Novatec PP, grade: MA1B) and hollow particles having a mass ratio of polypropylene resin to hollow particles of 90:10 was melted and mixed at 200°C, and placed in a hot press mold. After heating at 200°C for 15 minutes, the mixture was stirred with a scraper, and then loaded on a hot press set at 80°C. A barrel heated to 80°C was placed in the mold. When the surface temperature of the mold reached 140°C, it was pressurized at 15MPa, and then the mixture was taken out of the mold and pressurized at a pressure of less than 1MPa by a hot press set at 200°C to form a sheet-like molded body with a thickness of 0.3mm. The specific gravity of the obtained sheet-like molded body was measured, and the porosity residual rate of the hollow particles was calculated according to the following formula (D).

[0444] .

[0445] The symbols in formula (D) have the following meanings.

[0446] a: specific gravity of the sheet-like molded body after compression molding,

[0447] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value),

[0448] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0449] Table 1 shows the amount of material added (parts by mass) and the results of physical property evaluation for the hollow particles obtained in each Production Example.

[0450] The remaining void ratios of the press test method shown in Table 1 are average values ​​of 10 samples (n=10).

[0451] [Table 1]

[0452] .

[0453] [Production of Elastomer Composition, Production of Elastomer Molded Article]

[0454] [Example 1]

[0455] 100 parts by mass of ethylene-propylene-diene terpolymer (EPDM) (Mooney viscosity at 100°C (JIS K6300), ML (1+4) 100°C: 25, product name: Nordel IP 4725, manufactured by The Dow Chemical Company) was placed in a kneader (Plasti-Corder Lab-Station, manufactured by Brabender), and kneading was started at a kneading temperature of 100°C and a rotation speed of 50 rpm. While 25 parts by mass of the hollow particles A obtained in Production Example 1, 45 parts by mass of carbon (product name: Seast S, manufactured by Tokai Carbon Co., Ltd.), 29 parts by mass of silica (product name: Nipsil VN-3, manufactured by Tosoh Silicon Chemical Co., Ltd.), and 75 parts of a process oil (hydrogenated high viscosity oil: DIANAPROCESS OIL PW-300, manufactured by Idemitsu Kosan Co., Ltd.) as a plasticizer were added and pre-kneaded.

[0456] The pre-mixed mixture was preheated in an oven at 60°C for more than 1 hour before roll mixing, and the temperature of the mixture was maintained at 60°C.

[0457] The mixture preheated to 60°C was placed in a two-roll kneader (model name: DY6-15, roll diameter: 6 inches, roll gap: 0.5 mm, manufactured by Daihan Co., Ltd.) with the roll kneading temperature set to 80°C, and then, while adding 1.5 parts of sulfur as a vulcanizing agent and 2 parts of tetrathiuram monosulfide (reagent grade) as a vulcanization accelerator, roll kneading was performed (rotation speed: front roll 24 rpm / rear roll 21 rpm, kneading time: 15 minutes).

[0458] The molten mixture after roll kneading was dried by heating at 80° C. for 6 hours, thereby obtaining a hollow particle-containing elastomer composition of Example 1.

[0459] The obtained hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to prepare a sheet-shaped molded body (hollow particle-containing elastomer molded body) having a thickness of 0.3 mm.

[0460] [Example 2]

[0461] In Example 1, except that the preheating temperature was changed from 60° C. to 80° C., the same procedures as in Example 1 were followed to obtain a hollow particle-containing elastomer composition of Example 2.

[0462] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 1 to obtain a hollow particle-containing elastomer molded body of Example 2.

[0463] [Example 3]

[0464] In Example 1, except that 25 parts by mass of the hollow particles B obtained in Production Example 2 were used instead of 25 parts by mass of the hollow particles A obtained in Production Example 1, the same procedures as in Example 1 were followed to obtain a hollow particle-containing elastomer composition of Example 3.

[0465] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 1 to obtain a hollow particle-containing elastomer molded body of Example 3.

[0466] [Example 4]

[0467] The non-oil-extended styrene butadiene rubber used in Example 4 refers to a styrene butadiene rubber to which no oil component as a plasticizer is added.

[0468] 100 parts by mass of non-oil-extended styrene butadiene rubber (Mooney viscosity at 100°C (JIS K6300), ML (1+4) 100°C: 52.0, styrene unit content: 23.5% by mass, product name: Nipol (registered trademark) 1502, manufactured by Nippon Zeon Co., Ltd.) was charged into a kneader (Plasti-Corder Lab-Station, manufactured by Brabender), and kneading was started at a kneading temperature of 100°C and a rotation speed of 50 rpm. While kneading was started, 25 parts by mass of the hollow particles A obtained in Production Example 1, 25 parts by mass of carbon (product name: Seast S, manufactured by Tokai Carbon Co., Ltd.), 29 parts by mass of silica (product name: Nipsil VN-3, manufactured by Tosoh Silicon Chemical Co., Ltd.), and 65 parts of a process oil (hydrogenated high viscosity oil: DIANA PROCESS OIL) as a plasticizer were charged. PW-300, manufactured by Idemitsu Kosan Co., Ltd.), 10 parts by mass of liquid polybutadiene (weight average molecular weight: 2100, product name: liquid polybutadiene B2000, manufacturer: Nippon Soda Co., Ltd.) as a plasticizer having an olefinic double bond, were pre-kneaded.

[0469] The pre-mixed mixture was preheated in an oven at 60°C for more than 1 hour before roll mixing, and the temperature of the mixture was maintained at 60°C.

[0470] The mixture preheated to 60°C was placed in a two-roll kneader (model name: DY6-15, roll diameter: 6 inches, roll gap: 0.5 mm, manufactured by Daihan Co., Ltd.) with the roll kneading temperature set to 80°C, and then, while adding 1.5 parts of sulfur as a vulcanizing agent and 2 parts of tetrathiuram monosulfide (reagent grade) as a vulcanization accelerator, roll kneading was performed (rotation speed: front roll 24 rpm / rear roll 21 rpm, kneading time: 15 minutes).

[0471] The molten mixture after roll kneading was heated at 80° C. for 6 hours to be dried, thereby obtaining a hollow particle-containing elastomer composition of Example 4.

[0472] The obtained hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to prepare a sheet-shaped molded body (hollow particle-containing elastomer molded body) having a thickness of 0.3 mm.

[0473] [Example 5]

[0474] In Example 4, the same procedures as in Example 4 were followed, except that the amount of carbon was changed from 25 parts by mass to 45 parts by mass, the amount of processing oil as a plasticizer was changed from 65 parts by mass to 55 parts by mass, and the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 10 parts by mass to 20 parts by mass, to obtain the hollow particle-containing elastomer composition of Example 5.

[0475] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 4 to obtain a hollow particle-containing elastomer molded body of Example 5.

[0476] [Example 6]

[0477] In Example 4, the same procedures as in Example 4 were followed, except that the amount of carbon was changed from 25 parts by mass to 45 parts by mass, the amount of processing oil as a plasticizer was changed from 65 parts by mass to 0 parts by mass, and the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 10 parts by mass to 60 parts by mass, to obtain the hollow particle-containing elastomer composition of Example 6.

[0478] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 4 to obtain a hollow particle-containing elastomer molded body of Example 6.

[0479] [Example 7]

[0480] In Example 4, the amount of carbon was changed from 25 parts by mass to 45 parts by mass, the amount of processing oil as a plasticizer was changed from 65 parts by mass to 0 parts by mass, the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 10 parts by mass to 75 parts by mass, and the preheating temperature was changed from 60°C to 80°C as heating conditions. Except for this, the same procedures as in Example 4 were followed to obtain the hollow particle-containing elastomer composition of Example 7.

[0481] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 4 to obtain a hollow particle-containing elastomer molded body of Example 7.

[0482] [Example 8]

[0483] In Example 4, the same procedures as in Example 4 were followed, except that the amount of carbon was changed from 25 parts by mass to 45 parts by mass, the amount of processing oil as a plasticizer was changed from 65 parts by mass to 0 parts by mass, and the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 10 parts by mass to 80 parts by mass, to obtain the hollow particle-containing elastomer composition of Example 8.

[0484] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 4 to obtain a hollow particle-containing elastomer molded body of Example 8.

[0485] [Example 9]

[0486] The oil-extended styrene-butadiene rubber used in Example 9 refers to a styrene-butadiene rubber to which an oil component as a plasticizer is added in an amount of several mass %.

[0487] 100 parts by mass of oil-extended styrene butadiene rubber (Mooney viscosity at 100°C (JIS K6300), ML (1+4) 100°C: 49.0, styrene unit content: 40.0% by mass, product name: Nipol (registered trademark) 1739, manufactured by Nippon Zeon Co., Ltd.) was placed in a kneader (Plasti-Corder Lab-Station, manufactured by Brabender), and kneading was started at a kneading temperature of 100°C and a rotation speed of 50 rpm. While kneading was started, 25 parts by mass of the hollow particles A obtained in Preparation Example 1, 45 parts by mass of carbon (product name: Seast S, manufactured by Tokai Carbon Co., Ltd.), and 29 parts by mass of silica (product name: Nipsil VN-3, manufactured by Tosoh Silicone Chemicals Co., Ltd.), 60 parts by mass of liquid polybutadiene (weight average molecular weight: 2100, product name: liquid polybutadiene B2000, manufactured by Nippon Soda Co., Ltd.) as a plasticizer having an olefinic double bond, were pre-kneaded.

[0488] The pre-mixed mixture was preheated in an oven at 60°C for more than 1 hour before roll mixing, and the temperature of the mixture was maintained at 60°C.

[0489] The mixture preheated to 60°C was placed in a two-roll kneader (model name: DY6-15, roll diameter: 6 inches, roll gap: 0.5 mm, manufactured by Daihan Co., Ltd.) with the roll kneading temperature set to 80°C, and then, while adding 1.5 parts of sulfur as a vulcanizing agent and 2 parts of tetrathiuram monosulfide (reagent grade) as a vulcanization accelerator, roll kneading was performed (rotation speed: front roll 24 rpm / rear roll 21 rpm, kneading time: 15 minutes).

[0490] The molten mixture after roll kneading was dried by heating at 80° C. for 6 hours, thereby obtaining a hollow particle-containing elastomer composition of Example 9.

[0491] The obtained hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to prepare a sheet-shaped molded body (hollow particle-containing elastomer molded body) having a thickness of 0.3 mm.

[0492] [Example 10]

[0493] In Example 9, the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 60 parts by mass to 75 parts by mass, and the preheating temperature was changed from 60° C. to 80° C. as heating conditions. The same procedures as in Example 9 were followed to obtain the hollow particle-containing elastomer composition of Example 10.

[0494] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 9 to obtain a hollow particle-containing elastomer molded body of Example 10.

[0495] [Example 11]

[0496] In Example 9, except that the amount of liquid polybutadiene as a plasticizer having an ethylenic double bond was changed from 60 parts by mass to 80 parts by mass, the same procedures as in Example 9 were followed to obtain a hollow particle-containing elastomer composition of Example 11.

[0497] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 9 to obtain a hollow particle-containing elastomer molded body of Example 11.

[0498] [Example 12]

[0499] 100 parts by mass of butadiene rubber (Mooney viscosity at 100° C. (JIS K6300), ML (1+4) 100° C.: 44.0, content of styrene units: 0% by mass, product name: Nipol (registered trademark) BR1220, manufactured by Nippon Zeon Co., Ltd.) was placed in a kneader (Plasti-Corder Lab-Station, manufactured by Brabender), and kneading was started at a kneading temperature of 100° C. and a rotation speed of 50 rpm, while 25 parts by mass of the hollow particles A obtained in Production Example 1, 45 parts by mass of carbon (product name: Seast S, manufactured by Tokai Carbon Co., Ltd.), and 29 parts by mass of silica (product name: Nipsil VN-3, manufactured by Tosoh Silicone Chemicals Co., Ltd.), 60 parts by mass of liquid polybutadiene (weight average molecular weight: 2100, product name: liquid polybutadiene B2000, manufactured by Nippon Soda Co., Ltd.) as a plasticizer having an olefinic double bond, were pre-kneaded.

[0500] The pre-mixed mixture was preheated in an oven at 60°C for more than 1 hour before roll mixing, and the temperature of the mixture was maintained at 60°C.

[0501] The mixture preheated to 60°C was placed in a two-roll kneader (model name: DY6-15, roll diameter: 6 inches, roll gap: 0.5 mm, manufactured by Daihan Co., Ltd.) with the roll kneading temperature set to 80°C, and then, while adding 1.5 parts of sulfur as a vulcanizing agent and 2 parts of tetrathiuram monosulfide (reagent grade) as a vulcanization accelerator, roll kneading was performed (rotation speed: front roll 24 rpm / rear roll 21 rpm, kneading time: 15 minutes).

[0502] The molten mixture after roll kneading was dried by heating at 80° C. for 6 hours, thereby obtaining a hollow particle-containing elastomer composition of Example 12.

[0503] The obtained hollow particle-containing elastomer composition was press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to prepare a sheet-shaped molded body (hollow particle-containing elastomer molded body) having a thickness of 0.3 mm.

[0504] [Example 13]

[0505] In Example 12, the amount of liquid polybutadiene as a plasticizer having olefinic double bonds was changed from 60 parts by mass to 75 parts by mass, and the preheating temperature was changed from 60°C to 80°C as the heating conditions. The same procedures as in Example 12 were followed to obtain the hollow particle-containing elastomer composition of Example 13.

[0506] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 12 to obtain a hollow particle-containing elastomer molded body of Example 13.

[0507] [Example 14]

[0508] In Example 12, except that the amount of liquid polybutadiene as a plasticizer having an ethylenic double bond was changed from 60 parts by mass to 80 parts by mass, the same procedures as in Example 12 were followed to obtain a hollow particle-containing elastomer composition of Example 14.

[0509] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 12 to obtain a hollow particle-containing elastomer molded body of Example 14.

[0510] [Comparative Example 1]

[0511] In Example 1, except that preheating was not performed, the same procedures as in Example 1 were followed to obtain a hollow particle-containing elastomer composition of Comparative Example 1.

[0512] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 1 to obtain a hollow particle-containing elastomer molded body of Comparative Example 1.

[0513] [Comparative Example 2]

[0514] In Example 1, except that preheating was not performed and roll kneading was also performed without heating, the same procedures as in Example 1 were followed to obtain a hollow particle-containing elastomer composition of Comparative Example 2.

[0515] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 1 to obtain a hollow particle-containing elastomer molded body of Comparative Example 2.

[0516] [Comparative Example 3]

[0517] In Example 1, except that the amount of the plasticizer was changed to 30 parts by mass, the same procedures as in Example 1 were followed to obtain a hollow particle-containing elastomer composition of Comparative Example 3.

[0518] The obtained hollow particle-containing elastomer composition was press-molded under the same molding conditions as in Example 1 to obtain a hollow particle-containing elastomer molded body of Comparative Example 3.

[0519] [Evaluation of physical properties of hollow particle-containing elastomer composition and elastomer molded product]

[0520] 1. Determination of storage modulus G'

[0521] The hollow particle-containing elastomer composition obtained in each example and each comparative example, and the raw material mixture in the pre-mixing process stage obtained in each example and each comparative example were subjected to dynamic viscoelasticity measurement by the following method. In addition, the raw material mixture in the pre-mixing process stage is a simulated raw material mixture, and its formulation does not contain a vulcanizing agent and a vulcanization accelerator. If 1.5 parts of sulfur as a vulcanizing agent and 2 parts of tetrathiuram monosulfide as a vulcanization accelerator are added to the raw material mixture in the pre-mixing process stage, the formulation of the raw material mixture and the hollow particle-containing elastomer composition will be the same as the final formulation.

[0522] Based on the measurement results, the storage modulus G' of the elastomer composition at 60°C, the storage modulus G' of the raw material mixture at 60°C, the storage modulus G' of the raw material mixture at the temperature at the start of roll mixing (preheating temperature), and the storage modulus G' of the raw material mixture at the roll mixing temperature were determined.

[0523] [Method for dynamic viscoelasticity measurement]

[0524] The dynamic viscoelasticity measurement was performed using the model name HAAKE MARK III (manufactured by Thermo Fisher Scientific). The test piece was made of a hollow particle elastomer composition and a raw material mixture, and a 2 mm thick sheet was made by a press at 160°C, and then punched into a 20 mmφ shape by a punching machine. The test piece (2 mm thick) was welded with a 20 mmφ parallel plate set at a temperature of 170°C, and then installed in a dynamic viscoelasticity measuring device. While cooling from 170°C to room temperature at 5°C / min, the storage modulus G' (unit: MPa) from 150°C to room temperature was measured.

[0525] <Measurement conditions>

[0526] Frequency: 1Hz

[0527] Geometry: Parallel plate (20mmφ)

[0528] Strain: 0.001

[0529] Gap: 1.5mm

[0530] 2. Determination of residual porosity of hollow particle elastomer molded bodies

[0531] The specific gravity of the sheet-shaped elastomer molded body obtained in each of the Examples and Comparative Examples was measured, and the void residual ratio of the hollow particles in the elastomer molded body was calculated according to the following formula (D).

[0532] .

[0533] a: specific gravity of the sheet-like molded body obtained by press molding,

[0534] b: Specific gravity of the molded body assuming that the pores are maintained (calculated value),

[0535] c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

[0536] Table 2 shows the amounts (parts by mass) of materials added, kneading conditions, and physical property evaluation results for the elastomer compositions and elastomer molded products obtained in the respective Examples and Comparative Examples.

[0537] The residual porosity ratios of the elastomer molded bodies after press molding shown in Table 2 are average values ​​of 10 samples (n=10).

[0538] In addition, the kneading conditions in each Example and each Comparative Example are generally as follows.

[0539] <Premixing>

[0540] Equipment: Plasti-Corder Lab-Station (made by Brabender)

[0541] Compounding machine: W 250E

[0542] Blade: Roller type

[0543] Speed: 50rpm

[0544] Mixing temperature: 100℃

[0545] <Roller Mixing Conditions>

[0546] Equipment: Twin-roll mixer DY6-15 (manufactured by Daihan Co., Ltd.)

[0547] Roller diameter: 6 inches

[0548] Speed: front roller 24rpm / rear roller 21rpm

[0549] Roller spacing: 0.5mm

[0550] Set temperature: 25~80℃

[0551] Mixing time: 15 minutes

[0552] [Table 2-1]

[0553] .

[0554] [Table 2-2]

[0555] .

[0556] [discuss]

[0557] In Examples 1 and 3, a raw material mixture comprising a base elastomer and hollow particles is used, in which a resin forming a shell contains a polymer containing 50 parts by mass or more of cross-linking monomer units in 100 parts by mass of all monomer units, and the steps from pre-mixing to roll mixing are carried out at a pre-mixing temperature of 100°C, a pre-mixing speed of 50 rpm, a preheating temperature of 60°C, and a roll mixing temperature of 80°C to produce an elastomer composition.

[0558] As a result, in Example 1, the storage modulus of the elastomer composition at 60°C and the storage modulus of the raw material mixture after homogenization at 60°C were 1.7 MPa. In Example 3, the storage modulus of the elastomer composition at 60°C and the storage modulus of the raw material mixture after homogenization at 60°C were 1.6 MPa. Therefore, in Examples 1 and 3, the storage modulus of the elastomer composition at 60°C and the storage modulus of the raw material mixture after homogenization at 60°C were both 2.5 MPa or less.

[0559] The formulation of the raw material mixture in the pre-kneading stage differs from that of the finally obtained elastomer composition in that it does not contain a vulcanizing agent and a vulcanization accelerator. However, the storage modulus at 60° C. does not change significantly due to such a difference in composition.

[0560] Furthermore, the elastomer compositions obtained in Examples 1 and 3 were press-molded to produce sheet-like molded bodies. As a result, the residual porosity of the hollow particles present in the molded bodies was 100%, thereby confirming that the hollow particles were not easily broken during the molding process and a molded body with a high residual porosity was obtained.

[0561] In Example 1, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60° C., was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80° C., was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it can be considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0562] In Example 3, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60° C., was 1.6 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80° C., was 1.1 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it can be considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0563] In Example 2, the same raw material mixture as in Example 1 was used, and the steps from pre-mixing to roll mixing were carried out at a pre-mixing temperature of 100° C., a pre-mixing rotation speed of 50 rpm, a preheating temperature of 80° C., and a roll mixing temperature of 80° C. to produce an elastomer composition. The raw material mixture used in Example 2 and the obtained elastomer composition were the same as in Example 1, and therefore their storage modulus at 60° C. was 2.5 MPa or less.

[0564] Furthermore, a sheet-shaped molded body was produced by press-molding the elastomer composition obtained in Example 2. As a result, the residual porosity of the hollow particles present in the molded body was 100%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high residual porosity was obtained.

[0565] Example 1 and Example 2 used a raw material mixture with the same composition, but the temperature at the start of roll kneading of the raw material mixture (equal to the preheating temperature) was different. That is, the temperature at the start of roll kneading of Example 1 was 60°C, and the temperature at the start of roll kneading of Example 2 was 80°C. Although there is such a difference in process temperature, the porosity residual rate of the hollow particles in the elastomer molded bodies of Example 1 and Example 2 is 100%, and the difference in the difficulty of crushing the hollow particles is not seen from the results of the porosity residual rate alone. However, in Example 2, the temperature at the start of roll kneading of the raw material mixture and the roll kneading temperature of the raw material mixture are both 80°C. During the entire process from the initial stage to the end stage of roll kneading, the storage modulus of the raw material mixture at the process temperature, i.e., 80°C, is 1.2MPa, and the load caused by roll kneading is more suppressed than that in Example 1. Therefore, it can be considered that compared with Example 1, a kneading condition in which the hollow particles are less likely to break is achieved.

[0566] In Comparative Examples 1 and 2, the same raw material mixture as in Example 1 was used. The raw material mixture used in Comparative Examples 1 and 2 and the resulting elastomer composition had the same composition as in Example 1, and therefore their storage moduli at 60° C. were 2.5 MPa or less.

[0567] However, in Comparative Example 1, since no preheating was performed, the temperature at the start of roll kneading was as low as room temperature (25°C). The elastomer composition obtained in Comparative Example 1 was press-molded to produce a sheet-like molded body, and as a result, the porosity of the hollow particles present in the molded body was 75%. Although Comparative Example 1 used a raw material mixture having the same composition as Example 1, the storage modulus of the raw material mixture at the temperature of 25°C at the start of roll kneading was 4.6 MPa, which was greater than 2.5 MPa. Therefore, it can be considered that the load caused by roll kneading increased compared with Example 1 in the initial stage of roll kneading, and a large number of hollow particles were broken.

[0568] In Comparative Example 2, the preheating was not performed and the roll kneading step was performed at room temperature, so the roll kneading was performed at room temperature (25° C.) from the initial stage to the final stage. The elastomer composition obtained in Comparative Example 2 was press-molded to produce a sheet-like molded body. As a result, the void residual ratio of the hollow particles present in the molded body was 14%.

[0569] Although Comparative Example 2 used a raw material mixture having the same composition as that of Example 1 and Comparative Example 1, the storage modulus of the raw material mixture at the process temperature of 25° C. was 4.6 MPa, which was greater than 2.5 MPa, throughout the entire process from the initial stage to the final stage of roll kneading. Therefore, it is considered that the load caused by roll kneading was increased in the entire process from the initial stage to the final stage of roll kneading compared with Example 1 and Comparative Example 1, and a large number of hollow particles were broken.

[0570] In Comparative Example 3, the content of the plasticizer in the raw material mixture of Example 1 was reduced to 30 parts by mass. As a result, the storage modulus of the elastomer composition at 60°C and the storage modulus of the raw material mixture after homogenization at 60°C were both 3.2 MPa, which were greater than 2.5 MPa. In addition, the obtained elastomer composition was press-molded to produce a sheet-like molded body. As a result, the porosity of the hollow particles present in the molded body was 45%, and the initial porosity of the hollow particles could not be maintained.

[0571] In Comparative Example 3, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 3.2 MPa, and the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 2.2 MPa. Throughout the entire process from the initial stage to the final stage of roll kneading, the storage modulus of the raw material mixture at the process temperature, i.e., 60 to 80°C, was greater than 2.5 MPa. Therefore, it can be considered that the load caused by roll kneading increased in the entire process from the initial stage to the final stage of roll kneading compared with Example 1, and a large number of hollow particles were broken.

[0572] Examples 4 and 5 are examples in which the base elastomer in the raw material mixture of Example 1 was changed from EPDM to non-oil-extended styrene butadiene rubber, and part of the plasticizer having no reactive sites was replaced with a plasticizer having reactive sites.

[0573] In the raw material mixture of Example 4, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to non-oil-extended styrene butadiene rubber, the carbon content was changed from 45 parts by mass to 25 parts by mass, the content of the plasticizer (processing oil) in the raw material mixture of Example 1 was reduced from 75 parts by mass to 65 parts by mass, and 10 parts by mass of a plasticizer containing reactive sites (liquid polybutadiene) was added so that the total amount of the plasticizer and the plasticizer containing reactive sites was the same as the plasticizer content in Example 1, i.e., 75 parts by mass. The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a pre-heating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0574] As a result, the storage modulus at 60°C of the elastomer composition obtained in Example 4 and the storage modulus at 60°C of the raw material mixture after the homogenization treatment were 1.7 MPa, which were 2.5 MPa or less.

[0575] In the raw material mixture of Example 5, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to non-oil-extended styrene butadiene rubber, the content of the plasticizer (processing oil) was reduced from 75 parts by mass to 55 parts by mass, and 20 parts by mass of a plasticizer containing reactive sites (liquid polybutadiene) was added so that the total amount of the plasticizer and the plasticizer containing reactive sites was the same as the plasticizer content in Example 1, i.e., 75 parts by mass. The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0576] As a result, the storage modulus of the elastomer composition obtained in Example 5 at 60°C was 1.7 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.6 MPa, both of which were 2.5 MPa or less.

[0577] In Examples 4 and 5, since part of the plasticizer without reactive sites was replaced with the plasticizer containing reactive sites, a cross-linked structure may be formed between molecules of the base elastomer through the plasticizer containing reactive sites. However, since the amount of the plasticizer containing reactive sites used was small, no significant change was observed between the storage modulus of the raw material mixture at 60°C in the pre-mixing stage and the storage modulus of the obtained elastomer composition at 60°C.

[0578] Furthermore, the elastomer compositions obtained in Examples 4 and 5 were press-molded to produce sheet-like molded bodies. As a result, the residual porosity of the hollow particles present in the molded bodies was 100%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high residual porosity was obtained.

[0579] In Example 4, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.1 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it can be considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0580] In Example 5, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0581] Examples 6 to 8 are examples in which the base elastomer in the raw material mixture of Example 1 is changed from EPDM to non-oil-extended styrene butadiene rubber, and the plasticizer without reactive sites is changed to a plasticizer containing reactive sites.

[0582] In the raw material mixture of Example 6, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to non-oil-extended styrene butadiene rubber, and 60 parts by mass of a plasticizer containing reactive sites (liquid polybutadiene) was used instead of 75 parts by mass of a plasticizer (process oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0583] As a result, the storage modulus of the elastomer composition obtained in Example 6 at 60°C was 2.1 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0584] In Example 6, it can be considered that since a cross-linked structure is formed between the molecules of the base elastomer by the plasticizer containing reactive active points, the storage modulus of the obtained elastomer composition at 60°C becomes larger than the storage modulus of the raw material mixture at 60°C in the pre-mixing stage.

[0585] Furthermore, a sheet-shaped molded body was produced by press-molding the elastomer composition obtained in Example 6. As a result, the porosity residual rate of the hollow particles present in the molded body was 85%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0586] In Example 6, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.6 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed, and the hollow particles were not easily broken.

[0587] In the raw material mixture of Example 7, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to non-oil-extended styrene butadiene rubber, and 75 parts by mass of a plasticizer (liquid polybutadiene) containing reactive sites was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0588] As a result, the storage modulus of the elastomer composition obtained in Example 7 at 60°C was 1.9 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0589] In Example 7, the storage modulus of the elastomer composition at 60°C is larger than the storage modulus of the raw material mixture at the pre-mixing stage at 60°C, but the difference in storage modulus increase is smaller than that in Example 6. This is considered to be because the amount of the reactive site-containing plasticizer used in Example 7 is larger than that in Example 6. More specifically, it is considered that, in the elastomer composition of Example 7, the effect of increasing plasticity due to the increase in the amount of the reactive site-containing plasticizer used counteracts the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the reactive site-containing plasticizer, and thus the difference in storage modulus increase is smaller than that in Example 6.

[0590] Furthermore, a sheet-shaped molded body was produced by press-molding the elastomer composition obtained in Example 7. As a result, the porosity residual rate of the hollow particles present in the molded body was 90%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0591] In Example 7, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.6 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0592] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 7 were the same as those of Example 6, but the residual porosity of the molded body of Example 7 was 90%, which was higher than the residual porosity (85%) of the molded body of Example 6. The reason for this is considered to be that in the elastomer composition of Example 7, the effect of increasing plasticity due to the increase in the amount of the plasticizer containing a reactive site and the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site counteract each other. That is, due to the counteraction of the effect of increasing plasticity, the storage modulus of the raw material mixture rapidly decreases during the process of the roll kneading temperature of the raw material mixture rising from 60°C to 80°C, and therefore, the load caused by roll kneading is suppressed more than that of Example 6, and the hollow particles are not easily broken.

[0593] The raw material mixture of Example 8 is a raw material composition in which the base elastomer in the raw material mixture of Example 1 is changed from EPDM to non-oil-extended styrene butadiene rubber, and 80 parts by mass of a plasticizer (liquid polybutadiene) containing a reactive site is used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions are the same as those of Example 1, and the steps from pre-kneading to roll kneading are carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0594] As a result, the storage modulus of the elastomer composition obtained in Example 8 at 60°C was 1.6 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0595] In Example 8, although more reactive site-containing plasticizer is used than in Example 7, the storage modulus of the obtained elastomer composition at 60°C is still low and is comparable to that of Examples 4 and 5 in which the amount of reactive site-containing plasticizer used is small. This is considered to be because the reaction between molecules of the base elastomer to form a cross-linked structure by the reactive site-containing plasticizer reaches a saturated state, and the effect of increasing the storage modulus reaches an upper limit. In contrast, the content of the free reactive site-containing plasticizer not bonded to the base elastomer increases, so that the effect of increasing plasticity becomes dominant.

[0596] Furthermore, a sheet-shaped molded body was produced by press-molding the elastomer composition obtained in Example 8. As a result, the porosity residual rate of the hollow particles present in the molded body was 100%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0597] In Example 8, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.1 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed, and the hollow particles were not easily broken.

[0598] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 8 are almost the same as those of Examples 6 and 7, but the residual porosity of the molded body of Example 8 is 100%, which is higher than the residual porosity of the molded body of Examples 6 and 7. This is considered to be because, in the elastomer composition of Example 8, the effect of increasing the plasticity due to the increase in the amount of the plasticizer containing a reactive site is more dominant than the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site. That is, since the effect of increasing the plasticity is dominant, the storage modulus of the raw material mixture rapidly decreases during the process of increasing the roll kneading temperature of the raw material mixture from 60°C to 80°C, and therefore, the load caused by the roll kneading is suppressed more than that of Examples 6 and 7, and the hollow particles are not easily broken.

[0599] Examples 9 to 11 are examples in which the base elastomer in the raw material mixture of Example 1 is changed from EPDM to oil-extended styrene butadiene rubber, and the plasticizer without reactive sites is changed to a plasticizer containing reactive sites.

[0600] In the raw material mixture of Example 9, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to oil-extended styrene butadiene rubber, and 60 parts by mass of a plasticizer containing reactive sites (liquid polybutadiene) was used instead of 75 parts by mass of a plasticizer (process oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0601] As a result, the storage modulus of the elastomer composition obtained in Example 9 at 60°C was 2.2 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.6 MPa, both of which were 2.5 MPa or less.

[0602] In Example 9, it can be considered that since a cross-linked structure is formed between the molecules of the base elastomer by the plasticizer containing reactive active points, the storage modulus of the obtained elastomer composition at 60°C becomes larger than the storage modulus of the raw material mixture at 60°C in the pre-mixing stage.

[0603] In addition, the elastomer composition obtained in Example 9 was press-molded to produce a sheet-like molded body. As a result, the porosity residual rate of the hollow particles present in the molded body was 87%, which also confirmed that the hollow particles were not easily broken during the molding process and a molded body with a high porosity residual rate was obtained.

[0604] In Example 9, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60° C., was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80° C., was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0605] In the raw material mixture of Example 10, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to oil-extended styrene butadiene rubber, and 75 parts by mass of a plasticizer (liquid polybutadiene) containing a reactive site was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0606] As a result, the storage modulus of the elastomer composition obtained in Example 10 at 60°C was 1.9 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0607] In Example 10, the storage modulus of the elastomer composition at 60°C is larger than the storage modulus of the raw material mixture at the pre-mixing stage at 60°C, but the difference in storage modulus increase is smaller than that of Example 9. This is considered to be because the amount of the reactive site-containing plasticizer used in Example 10 is larger than that of the reactive site-containing plasticizer used in Example 9. More specifically, it is considered that in the elastomer composition of Example 10, the effect of increasing plasticity due to the increase in the amount of the reactive site-containing plasticizer used counteracts the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the reactive site-containing plasticizer, and thus the difference in storage modulus increase is smaller than that of Example 9.

[0608] In addition, the elastomer composition obtained in Example 10 was press-molded to produce a sheet-like molded body. As a result, the porosity of the hollow particles present in the molded body was 90%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0609] In Example 10, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.6 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0610] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 10 are almost the same as those of Example 9, but the residual porosity of the molded body of Example 10 is 90%, which is higher than the residual porosity (87%) of the molded body of Example 9. The reason for this is considered to be that in the elastomer composition of Example 10, the effect of increasing plasticity due to the increase in the amount of the plasticizer containing a reactive site and the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site are opposed. That is, due to the opposition of the effect of increasing plasticity, the storage modulus of the raw material mixture rapidly decreases during the process of the roll kneading temperature of the raw material mixture rising from 60°C to 80°C, and therefore, the load caused by roll kneading is suppressed more than that of Example 9, and the hollow particles are not easily broken.

[0611] In the raw material mixture of Example 11, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to oil-extended styrene butadiene rubber, and 80 parts by mass of a plasticizer containing reactive sites (liquid polybutadiene) was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0612] As a result, the storage modulus of the elastomer composition obtained in Example 11 at 60°C was 1.6 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0613] In Example 11, although more reactive site-containing plasticizer was used than in Example 10, the storage modulus of the obtained elastomer composition at 60° C. was lower than that of Example 10. This is considered to be because the reaction between molecules of the base elastomer to form a cross-linked structure by the reactive site-containing plasticizer reached a saturated state, and the effect of increasing the storage modulus reached the upper limit, while the content of the free reactive site-containing plasticizer not bonded to the base elastomer increased, and the effect of increasing plasticity became dominant.

[0614] In addition, the elastomer composition obtained in Example 11 was press-molded to produce a sheet-like molded body. As a result, the porosity residual rate of the hollow particles present in the molded body was 100%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0615] In Example 11, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0616] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 11 were almost the same as those of Examples 9 and 10, but the residual porosity of the molded body of Example 11 was 100%, which was higher than the residual porosity of the molded body of Examples 9 and 10. This is considered to be because, in the elastomer composition of Example 11, the effect of increasing the plasticity due to the increase in the amount of the plasticizer containing a reactive site was more dominant than the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site. That is, since the effect of increasing the plasticity was dominant, the storage modulus of the raw material mixture rapidly decreased during the process of increasing the roll kneading temperature of the raw material mixture from 60°C to 80°C, and therefore the load caused by the roll kneading was suppressed more than that of Examples 9 and 10, and the hollow particles were not easily broken.

[0617] Examples 12 to 14 are examples in which the base elastomer in the raw material mixture of Example 1 was changed from EPDM to butadiene rubber, and the plasticizer having no reactive sites was changed to a plasticizer having reactive sites.

[0618] In the raw material mixture of Example 12, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to butadiene rubber, and 60 parts by mass of a plasticizer (liquid polybutadiene) containing a reactive site was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0619] As a result, the storage modulus of the elastomer composition obtained in Example 12 at 60°C was 2.5 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0620] In Example 12, it can be considered that since a cross-linked structure is formed between molecules of the base elastomer by the plasticizer containing reactive active points, the storage modulus of the obtained elastomer composition at 60°C becomes larger than the storage modulus of the raw material mixture at 60°C in the pre-mixing stage.

[0621] In addition, the elastomer composition obtained in Example 12 was press-molded to produce a sheet-like molded body. As a result, the porosity of the hollow particles present in the molded body was 85%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity retention rate was obtained.

[0622] In Example 12, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.6 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0623] In the raw material mixture of Example 13, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to butadiene rubber, and 75 parts by mass of a plasticizer (liquid polybutadiene) containing a reactive site was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0624] As a result, the storage modulus of the elastomer composition obtained in Example 13 at 60°C was 2.3 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.7 MPa, both of which were 2.5 MPa or less.

[0625] In Example 13, the storage modulus of the elastomer composition at 60°C is larger than the storage modulus of the raw material mixture at the pre-mixing stage at 60°C, but the difference in storage modulus increase is smaller than that in Example 12. This is considered to be because the amount of the reactive site-containing plasticizer used in Example 13 is larger than that in Example 12. More specifically, it is considered that in the elastomer composition of Example 13, the effect of increasing plasticity due to the increase in the amount of the reactive site-containing plasticizer used counteracts the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the reactive site-containing plasticizer, and thus the difference in storage modulus increase is smaller than that in Example 12.

[0626] In addition, a sheet-like molded body was produced by press-molding the elastomer composition obtained in Example 13. As a result, the porosity residual rate of the hollow particles present in the molded body was 90%. This also confirmed that the hollow particles were not easily broken during the molding process, and a molded body with a high porosity residual rate was obtained.

[0627] In Example 13, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60°C, was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80°C, was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0628] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 13 are almost the same as those of Example 12, but the residual porosity of the molded body of Example 13 is 90%, which is higher than the residual porosity (85%) of the molded body of Example 12. The reason for this is considered to be that in the elastomer composition of Example 13, the effect of increasing plasticity due to the increase in the amount of the plasticizer containing a reactive site and the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site are opposed. That is, due to the opposition of the effect of increasing plasticity, the storage modulus of the raw material mixture rapidly decreases during the process of the roll kneading temperature of the raw material mixture rising from 60°C to 80°C, and therefore, the load caused by roll kneading is suppressed more than that of Example 12, and the hollow particles are not easily broken.

[0629] In the raw material mixture of Example 14, the base elastomer in the raw material mixture of Example 1 was changed from EPDM to butadiene rubber, and 80 parts by mass of a plasticizer (liquid polybutadiene) containing a reactive site was used instead of 75 parts by mass of a plasticizer (processing oil). The kneading conditions were the same as those in Example 1, and the steps from pre-kneading to roll kneading were carried out at a pre-kneading temperature of 100° C., a pre-kneading speed of 50 rpm, a preheating temperature of 60° C., and a roll kneading temperature of 80° C. to produce an elastomer composition.

[0630] As a result, the storage modulus of the elastomer composition obtained in Example 14 at 60°C was 2.2 MPa, and the storage modulus of the raw material mixture after the homogenization treatment at 60°C was 1.6 MPa, both of which were 2.5 MPa or less.

[0631] In Example 14, although more reactive site-containing plasticizer was used than in Example 13, the storage modulus of the obtained elastomer composition at 60° C. was lower than that in Example 13. This is considered to be because the reaction between molecules of the base elastomer to form a cross-linked structure by the reactive site-containing plasticizer reached a saturated state, and the effect of increasing the storage modulus reached its upper limit, while the content of the free reactive site-containing plasticizer not bonded to the base elastomer increased, and the effect of increasing plasticity became dominant.

[0632] In addition, the elastomer composition obtained in Example 14 was press-molded to produce a sheet-like molded body. As a result, the porosity residual rate of the hollow particles present in the molded body was 100%, which also confirmed that the hollow particles were not easily broken during the molding process and a molded body with a high porosity residual rate was obtained.

[0633] In Example 14, the storage modulus of the raw material mixture at the temperature at the start of roll kneading (equal to the preheating temperature), i.e., 60° C., was 1.7 MPa, which was 2.5 MPa or less, while the storage modulus of the raw material mixture at the roll kneading temperature, i.e., 80° C., was 1.2 MPa, which was lower than the storage modulus at the start of roll kneading. Therefore, it is considered that the load caused by roll kneading was suppressed and the hollow particles were not easily broken.

[0634] The storage modulus of the raw material mixture at the roll kneading start temperature (60°C) and the storage modulus of the raw material mixture at the roll kneading temperature (80°C) of Example 14 were almost the same as those of Examples 12 and 13, but the residual porosity of the molded body of Example 14 was 100%, which was higher than the residual porosity of the molded bodies of Examples 12 and 13. This is considered to be because, in the elastomer composition of Example 14, the effect of increasing the plasticity due to the increase in the amount of the plasticizer containing a reactive site was more dominant than the effect of increasing the storage modulus due to the formation of a cross-linked structure between molecules of the base elastomer by the plasticizer containing a reactive site. That is, since the effect of increasing the plasticity was dominant, the storage modulus of the raw material mixture rapidly decreased during the process of increasing the roll kneading temperature of the raw material mixture from 60°C to 80°C, and therefore the load caused by the roll kneading was suppressed more than that of Examples 12 and 13, and the hollow particles were not easily broken.

[0635] Description of Reference Numerals

[0636] 1: Water-based medium;

[0637] 2: Low polarity materials;

[0638] 3: Dispersion stabilizer;

[0639] 4: Monomer composition;

[0640] 4a: hydrophobic solvent;

[0641] 4b: Materials other than hydrophobic solvents;

[0642] 4c: polymerizable monomer dispersed in an aqueous medium;

[0643] 5: Oil-soluble polymerization initiator;

[0644] 6: Shell;

[0645] 7: hollow part;

[0646] 8: Droplet;

[0647] 9: Precursor particles;

[0648] 10: Hollow particles whose hollow parts are filled with gas.

Claims

1. A hollow particle-containing elastomer composition comprising at least a base elastomer and hollow particles, The hollow particles have a shell composed of a resin and a hollow part surrounded by the shell, wherein the shell contains, as the resin, a polymer containing 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units, The hollow particle-containing elastomer composition has a storage modulus G′ of 2.5 MPa or less at 60° C. obtained by dynamic viscoelasticity measurement. The hollow particle-containing elastomer composition is used to prepare a sheet-shaped molded body according to the following method for measuring the residual porosity of a hollow particle-containing elastomer molded body, and the residual porosity measured is 80% or more. [Method for measuring the residual porosity of hollow particle-containing elastomer molded body] The hollow particle-containing elastomer composition is press-molded at a pressure of 1 MPa or less using a hot press at 120° C. to produce a sheet-like hollow particle-containing elastomer molded body. The specific gravity of the obtained elastomer molded body was measured, and the porosity residual rate of the hollow particles in the elastomer molded body was calculated according to the following formula (D): a: specific gravity of the sheet-like molded body after pressing, b: Specific gravity of the molded body assuming that the pores are maintained (calculated value), c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

2. The hollow particle-containing elastomer composition according to claim 1, wherein The hollow particles have a residual porosity of 80% or more as measured by the following compression test method. [Compression test method] A mixture of polypropylene resin and hollow particles in a mass ratio of polypropylene resin to hollow particles of 90:10 was melted and mixed at 200°C, placed in a hot press mold, heated at 200°C for 15 minutes and stirred, and then loaded on a hot press set at 80°C. A barrel heated to 80°C was placed in the mold. When the surface temperature of the mold reached 140°C, it was pressurized at 15 MPa. The mixture was then taken out of the mold and pressed at a pressure of 1 MPa or less by a hot press set at 200°C to form a sheet. The specific gravity of the obtained sheet-like molded body was measured, and the porosity residual rate of the hollow particles was calculated according to the following formula (D). The meanings of the symbols in formula (D) are as follows: a: specific gravity of the sheet-like molded body after compression molding, b: Specific gravity of the molded body assuming that the pores are maintained (calculated value), c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

3. The hollow particle-containing elastomer composition according to claim 1 or 2, wherein The porosity of the hollow particles is greater than 50%.

4. The hollow particle-containing elastomer composition according to any one of claims 1 to 3, wherein The hollow particles have a volume average particle size of 5.0 μm or more and 40.0 μm or less.

5. The hollow particle-containing elastomer composition according to any one of claims 1 to 4, wherein The polymer contains a trifunctional or higher crosslinking monomer unit derived from a trifunctional or higher crosslinking monomer as the crosslinking monomer unit, and the content of the trifunctional or higher crosslinking monomer unit is 10 parts by mass or more and 50 parts by mass or less in 100 parts by mass of all monomer units of the polymer.

6. The hollow particle-containing elastomer composition according to any one of claims 1 to 5, wherein The polymer contains, as the crosslinking monomer units, a bifunctional crosslinking monomer unit derived from a bifunctional crosslinking monomer and a trifunctional or higher crosslinking monomer unit derived from a trifunctional or higher crosslinking monomer.

7. The hollow particle-containing elastomer composition according to claim 6, wherein: The content of the trifunctional or higher crosslinkable monomer unit is 5 parts by mass or more and 40 parts by mass or less in 100 parts by mass of the total of the bifunctional crosslinkable monomer unit and the trifunctional or higher crosslinkable monomer unit.

8. The hollow particle-containing elastomer composition according to any one of claims 1 to 7, wherein The base elastomer is at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, styrene butadiene rubber, natural rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, butyl rubber, fluororubber, silicone rubber, acrylonitrile butadiene rubber, chloroprene rubber, acrylic rubber, chlorosulfonated polyethylene rubber, chlorinated polyethylene rubber, polyurethane rubber, isobutylene isoprene rubber, polysulfide rubber, propylene oxide rubber and epichlorohydrin rubber.

9. The hollow particle-containing elastomer composition according to claim 8, wherein At least a part of the base elastic body is at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, and styrene butadiene rubber.

10. The hollow particle-containing elastomer composition according to any one of claims 1 to 9, wherein The hollow particle-containing elastomer composition contains 35 to 100 parts by mass of a plasticizer based on 100 parts by mass of the base elastomer.

11. The hollow particle-containing elastomer composition according to claim 10, wherein At least a portion of the base elastomer is at least one selected from butadiene rubber and styrene butadiene rubber, and at least a portion of the plasticizer is a polymer having a reactive site that bonds to the base elastomer and a weight average molecular weight of 1,000 to 100,000.

12. The hollow particle-containing elastomer composition according to any one of claims 1 to 11, wherein The base elastic body has a Mooney viscosity (ML (1+4) 100° C.) of 20 or more and 75 or less as measured in accordance with JIS K6300.

13. The hollow particle-containing elastomer composition according to any one of claims 1 to 12, wherein The content ratio of the styrene monomer unit contained in the base elastic body is 0 mass % or more and 60 mass % or less.

14. A method for producing a hollow particle-containing elastomer composition, which is a method for producing a hollow particle-containing elastomer composition comprising at least a base elastomer and hollow particles, wherein: Preparing a raw material mixture containing at least a base elastomer and hollow particles, wherein the hollow particles have a shell containing a resin and a hollow portion surrounded by the shell, wherein the shell contains a polymer containing 50 parts by mass or more of a crosslinkable monomer unit in 100 parts by mass of all monomer units as the resin, and wherein the raw material mixture has a storage modulus G′ of 2.5 MPa or less at 60° C. obtained by dynamic viscoelasticity measurement after homogenization of the compounded components; Pre-kneading the raw material mixture using an internal mixer at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less; Immediately after pre-mixing, or after preheating to a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less, the raw material mixture is kneaded at a temperature at which the storage modulus G′ obtained by the dynamic viscoelasticity measurement after the homogenization treatment becomes 2.5 MPa or less.

15. The method for producing a hollow particle-containing elastomer composition according to claim 14, wherein: In the pre-kneading, the raw material mixture is pre-kneaded at a kneading temperature of 100° C. or higher using an internal kneading machine.

16. The method for producing a hollow particle-containing elastomer composition according to claim 14 or 15, wherein: In the case where preheating is not performed, kneading of the raw material mixture is started within 10 minutes after the pre-kneading.

17. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 16, wherein: In the preheating, the preheating temperature is 60° C. or higher.

18. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 17, wherein: In the kneading, the kneading temperature is 60° C. or higher.

19. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 18, wherein: The kneading step is performed by roll kneading.

20. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 19, wherein: The hollow particles have a residual porosity of 80% or more as measured by the following compression test method. [Compression test method] A mixture of polypropylene resin and hollow particles in a mass ratio of polypropylene resin to hollow particles of 90:10 was melted and mixed at 200°C, placed in a hot press mold, heated at 200°C for 15 minutes and stirred, and then loaded on a hot press set at 80°C. A barrel heated to 80°C was placed in the mold. When the surface temperature of the mold reached 140°C, it was pressurized at 15 MPa. The mixture was then taken out of the mold and pressed at a pressure of 1 MPa or less by a hot press set at 200°C to form a sheet. The specific gravity of the obtained sheet-like molded body was measured, and the porosity residual rate of the hollow particles was calculated according to the following formula (D). The meanings of the symbols in formula (D) are as follows: a: specific gravity of the sheet-like molded body after compression molding, b: Specific gravity of the molded body assuming that the pores are maintained (calculated value), c: Specific gravity of a molded body assuming that all hollow particles are crushed (calculated value).

21. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 20, wherein: The porosity of the hollow particles is greater than 50%.

22. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 21, wherein: The hollow particles have a volume average particle size of 5.0 μm or more and 40.0 μm or less.

23. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 22, wherein: The polymer contains a trifunctional or higher crosslinking monomer unit derived from a trifunctional or higher crosslinking monomer as the crosslinking monomer unit, and the content of the trifunctional or higher crosslinking monomer unit is 10 parts by mass or more and 50 parts by mass or less in 100 parts by mass of all monomer units of the polymer.

24. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 23, wherein: The polymer contains, as the crosslinking monomer units, a bifunctional crosslinking monomer unit derived from a bifunctional crosslinking monomer and a trifunctional or higher crosslinking monomer unit derived from a trifunctional or higher crosslinking monomer.

25. The method for producing a hollow particle-containing elastomer composition according to claim 24, wherein: The content of the trifunctional or higher crosslinkable monomer unit is 5 parts by mass or more and 40 parts by mass or less in 100 parts by mass of the total of the bifunctional crosslinkable monomer unit and the trifunctional or higher crosslinkable monomer unit.

26. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 25, wherein: The base elastomer is at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, styrene butadiene rubber, natural rubber, isoprene rubber, nitrile rubber, hydrogenated nitrile rubber, butyl rubber, fluororubber, silicone rubber, acrylonitrile butadiene rubber, chloroprene rubber, acrylic rubber, chlorosulfonated polyethylene rubber, chlorinated polyethylene rubber, polyurethane rubber, isobutylene isoprene rubber, polysulfide rubber, propylene oxide rubber and epichlorohydrin rubber.

27. The method for producing a hollow particle-containing elastomer composition according to claim 26, wherein: At least a part of the base elastic body is at least one selected from ethylene-α-olefin-non-conjugated diene copolymer rubber, butadiene rubber, and styrene butadiene rubber.

28. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 27, wherein: The raw material mixture contains 35 to 100 parts by mass of the plasticizer based on 100 parts by mass of the base elastic body.

29. The method for producing a hollow particle-containing elastomer composition according to claim 28, wherein: At least a portion of the base elastomer is at least one selected from butadiene rubber and styrene butadiene rubber, and at least a portion of the plasticizer is a polymer having a reactive site that bonds to the base elastomer and a weight average molecular weight of 1,000 to 100,000.

30. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 29, wherein: The base elastic body has a Mooney viscosity (ML (1+4) 100° C.) of 20 or more and 75 or less as measured in accordance with JIS K6300.

31. The method for producing a hollow particle-containing elastomer composition according to any one of claims 14 to 30, wherein: The content ratio of the styrene monomer unit contained in the base elastic body is 0 mass % or more and 60 mass % or less.